Composition for an adhesive layer for a non-aqueous secondary battery, an adhesive layer for a non-aqueous secondary battery and a method for manufacturing the same, a laminate for a non-aqueous secondary battery and a method for manufacturing the same, and, a non-aqueous secondary battery

KR103032270B1Active Publication Date: 2026-10-13ZEON CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
KR1020237031124
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-30
Filing Date
2022-03-17
Publication Date
2026-10-13
Estimated Expiration
2042-03-17

Smart Images

  • Figure 112023100661711-PCT00003_ABST
    Figure 112023100661711-PCT00003_ABST
Patent Text Reader

Abstract

The present invention aims to provide an adhesive layer for a non-aqueous secondary battery that can firmly bond battery components together under room temperature pressure while securing inkjet ejection characteristics, and also to provide a composition for an adhesive layer for a non-aqueous secondary battery that can exhibit excellent battery characteristics in a non-aqueous secondary battery. The composition for an adhesive layer for a non-aqueous secondary battery according to the present invention comprises a particulate polymer and is characterized in that the value of the pressure sensitivity of the adhesive strength obtained by the following formula (1) is greater than 20 and less than 80. Pressure sensitivity of adhesive force (N / (m·MPa)) = (T3 - T1) / 2···(1) (In the formula, T1 represents the adhesion strength (N / m) of a polyethylene separator and an adhesive layer for a non-aqueous secondary battery obtained from a polyethylene separator and a composition for a non-aqueous secondary battery adhesive layer when the two layers are pressure-bonded at 25°C and a pressure of 1 MPa for 10 seconds, and T3 represents the adhesion strength (N / m) of a polyethylene separator and an adhesive layer for a non-aqueous secondary battery obtained from a polyethylene separator and a composition for a non-aqueous secondary battery adhesive layer when the two layers are pressure-bonded at 25°C and a pressure of 3 MPa for 10 seconds.)
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a composition for an adhesive layer for a non-aqueous secondary battery, an adhesive layer for a non-aqueous secondary battery and a method for manufacturing the same, a laminate for a non-aqueous secondary battery and a method for manufacturing the same, and a non-aqueous secondary battery. Background Technology

[0002] Non-aqueous secondary batteries, such as lithium-ion secondary batteries (hereinafter also referred to as "secondary batteries"), are used for a wide range of applications due to their characteristics of being small, lightweight, having high energy density, and capable of repeated charging and discharging. Additionally, secondary batteries generally comprise battery components such as a positive electrode, a negative electrode, and a separator that isolates the positive and negative electrodes to prevent a short circuit between them.

[0003] In secondary batteries, a battery member having an adhesive layer formed thereon is used to improve adhesion between battery members. Specifically, an electrode formed by further forming an adhesive layer on an electrode substrate formed by forming an electrode composite layer on a current collector, or a separator formed by forming an adhesive layer on a separator substrate, is used as a battery member. This adhesive layer is typically formed by supplying a non-aqueous secondary battery adhesive layer composition (hereinafter also referred to as "adhesive layer composition") in the form of a slurry containing a binder component and a solvent such as water onto a substrate such as an electrode substrate or a separator substrate, and drying it.

[0004] In recent years, in order to strongly bond battery components together, exhibit excellent battery characteristics in secondary batteries, and further increase the manufacturing efficiency of secondary batteries, it has been considered to form an adhesive layer (adhesive material) by extruding a composition for the adhesive layer as a fine droplet from a nozzle using an inkjet method.

[0005] For example, Patent Document 1 describes a non-aqueous secondary battery slurry comprising a particulate polymer having a core-shell structure, a predetermined amount of polyhydric alcohol compound, and water, which is coated by an inkjet method. Furthermore, Patent Document 1 reports that by using the said non-aqueous secondary battery slurry, even when the inkjet method is employed, an adhesive material can be efficiently applied to the surface of a battery member while ensuring strong adhesion between battery members and excellent low-temperature output characteristics of the secondary battery.

[0006] In addition, Patent Document 2 describes a composition for an adhesive layer comprising organic particles having a core-shell structure, a thixotropic agent, and water, satisfying a predetermined appearance, which is coated by an inkjet method. Furthermore, Patent Document 2 reports that by using the said composition for the adhesive layer, an adhesive layer can be formed well even when using an inkjet method, and a substrate and a substrate can be firmly bonded through said adhesive layer. Prior art literature

[0007] International Release No. 2019 / 221056 International Release No. 2020 / 045246 The problem to be solved

[0008] However, according to the inventors' review, it has been revealed that although the above-described non-aqueous secondary battery slurry or adhesive layer composition of the prior art can be well coated onto a battery member by an inkjet method, when battery members are bonded together under room temperature pressure by interposing an adhesive layer (adhesive material) formed by drying the coated adhesive layer composition during the secondary battery manufacturing process, the adhesive strength between the battery members is insufficient, which impairs the productivity of the secondary battery and also degrades the battery characteristics.

[0009] In other words, the aforementioned conventional technology still had room for improvement in terms of securing inkjet ejection characteristics, firmly bonding battery components together under room-temperature pressure, and imparting excellent battery characteristics to the secondary battery.

[0010] Accordingly, the present invention aims to provide an adhesive layer for a non-aqueous secondary battery that can firmly bond battery components together under room temperature pressure while securing inkjet ejection characteristics, and also to provide a composition for an adhesive layer for a non-aqueous secondary battery that can exhibit excellent battery characteristics in a non-aqueous secondary battery.

[0011] In addition, the present invention aims to provide an adhesive layer for a non-aqueous secondary battery that can firmly bond battery components together under pressure at room temperature and also exhibit excellent electrical characteristics in the non-aqueous secondary battery.

[0012] In addition, the present invention aims to provide a laminate for a non-aqueous secondary battery capable of exhibiting excellent electrical characteristics in a non-aqueous secondary battery.

[0013] In addition, the present invention aims to provide a non-aqueous secondary battery with excellent electrical characteristics.

[0014] Furthermore, the present invention aims to provide a method for manufacturing an adhesive layer for a non-aqueous secondary battery that can firmly bond battery members together by applying pressure at room temperature and also exhibit excellent electrical characteristics in the non-aqueous secondary battery.

[0015] In addition, the present invention aims to provide a method for manufacturing a laminate for a non-aqueous secondary battery capable of exhibiting excellent electrical characteristics in a non-aqueous secondary battery. means of solving the problem

[0016] The inventors of the present invention conducted a thorough investigation with the aim of solving the above problem. The inventors discovered that by using a composition for a non-aqueous secondary battery adhesive layer obtained from a polyethylene separator and a composition for a non-aqueous secondary battery adhesive layer, the degree of change in adhesive strength (pressure sensitivity) satisfies a predetermined relationship when the adhesive layer is pressure-bonded at different pressures under predetermined conditions, it is possible to firmly bond battery components together under pressure at room temperature while securing inkjet ejection characteristics, and also to exhibit excellent battery characteristics in a non-aqueous secondary battery, and thus completed the present invention.

[0017] That is, the composition for a non-aqueous secondary battery adhesive layer of the present invention, which is intended to advantageously solve the above problem, is a composition for a non-aqueous secondary battery adhesive layer comprising a particulate polymer, characterized in that the value of the pressure sensitivity of the adhesive force obtained by the following formula (1) is greater than 20 and less than 80.

[0018] Pressure sensitivity of adhesive force (N / (m·MPa)) = (T3 - T1) / 2···(1)

[0019] (In the formula, T1 represents the adhesive strength (N / m) of a polyethylene separator and an adhesive layer for a non-aqueous secondary battery obtained from a polyethylene separator and a composition for a non-aqueous secondary battery adhesive layer when the two layers are bonded by pressure bonding at 25°C and a pressure of 1 MPa for 10 seconds, and T3 represents the adhesive strength (N / m) of a polyethylene separator and an adhesive layer for a non-aqueous secondary battery obtained from a polyethylene separator and a composition for a non-aqueous secondary battery adhesive layer when the two layers are bonded by pressure bonding at 25°C and a pressure of 3 MPa for 10 seconds.) Thus, by using a composition for a non-aqueous secondary battery adhesive layer in which the pressure sensitivity of the adhesive strength is within a predetermined range, it is possible to firmly bond battery components together by pressure at room temperature while securing inkjet ejection characteristics, and also to exhibit excellent battery characteristics in a non-aqueous secondary battery.

[0020] Meanwhile, in the present invention, the pressure sensitivity of the adhesive force can be measured by the method described in the example.

[0021] In addition, the composition for a non-aqueous secondary battery adhesive layer of the present invention preferably has a core-shell structure in which the particulate polymer comprises a core portion and a shell portion that partially covers the outer surface of the core portion, wherein the glass transition temperature of the core portion is -50°C or higher and 25°C or lower, the glass transition temperature of the shell portion is 50°C or higher and 200°C or lower, and the mass ratio of the shell portion to the total of the core portion and the shell portion is 2% or higher and 15% or lower. Thus, by using a particulate polymer having a core-shell structure comprising a core portion and a shell portion that partially covers the outer surface of the core portion, wherein the glass transition temperature of the core portion and the glass transition temperature of the shell portion are each within a predetermined range, and the mass ratio of the shell portion to the total of the core portion and the shell portion is within a predetermined range, it is possible to further suppress nozzle clogging when using an inkjet method and further improve inkjet ejection characteristics, while simultaneously bonding battery members more firmly at room temperature and exhibiting even better battery characteristics in a non-aqueous secondary battery.

[0022] Meanwhile, in the present invention, the “glass transition temperature” can be measured using the measurement method described in the embodiments of this specification.

[0023] In addition, the composition for a non-aqueous secondary battery adhesive layer of the present invention preferably has a glass transition temperature of the core portion of -40°C or higher and 25°C or lower. In this way, if the glass transition temperature of the core portion is within the above predetermined range, the inkjet ejection characteristics can be further improved.

[0024] In addition, the composition for a non-aqueous secondary battery adhesive layer of the present invention preferably has a volume average particle size of the particulate polymer of 100 nm or more and 1500 nm or less. If the volume average particle size of the particulate polymer is 100 nm or more, it is possible to suppress the deterioration of battery characteristics caused by an increase in resistance of the secondary battery due to hindering the lithium ion path of the substrate (electrode or separator). In addition, if the volume average particle size is 1500 nm or less, it is possible to further suppress nozzle clogging when the composition for a non-aqueous secondary battery adhesive layer is coated by an inkjet method, thereby improving inkjet ejection characteristics.

[0025] Meanwhile, in the present invention, "volume average particle size" refers to a particle size at which the cumulative volume calculated from the small size side is 50% in the volume-based particle size distribution measured by laser diffraction, and can be measured using the measurement method described in the embodiments of this specification.

[0026] Furthermore, the present invention aims to advantageously solve the above problem, and the adhesive layer for a non-aqueous secondary battery according to the present invention is characterized by being formed using any one of the compositions for an adhesive layer for a non-aqueous secondary battery described above. In this way, the adhesive layer for a non-aqueous secondary battery formed using any one of the compositions for an adhesive layer for a non-aqueous secondary battery described above can firmly bond battery components, such as separators or electrodes, to each other by applying pressure at room temperature, while simultaneously enabling excellent battery characteristics in the non-aqueous secondary battery.

[0027] Furthermore, the present invention aims to advantageously solve the above problem. The method for manufacturing an adhesive layer for a non-aqueous secondary battery according to the present invention is characterized by comprising the steps of: coating any one of the above-described compositions for an adhesive layer for a non-aqueous secondary battery onto a substrate by an inkjet method; and drying the composition for an adhesive layer for a non-aqueous secondary battery coated onto the substrate. In this way, by using any one of the above-described compositions for an adhesive layer for a non-aqueous secondary battery, even when an inkjet method is employed, the occurrence of nozzle clogging is suppressed and inkjet ejection characteristics can be secured, thereby enabling the good formation of an adhesive layer for a non-aqueous secondary battery on a substrate.

[0028] Furthermore, the present invention aims to advantageously solve the above problem. The laminate for a non-aqueous secondary battery according to the present invention is a laminate for a non-aqueous secondary battery comprising an electrode and a separator, wherein the electrode and the separator are bonded together via the adhesive layer for a non-aqueous secondary battery described above. In this way, the laminate for a non-aqueous secondary battery having battery members bonded together using the adhesive layer for a non-aqueous secondary battery described above has the battery members bonded together strongly, thereby enabling excellent battery characteristics to be exhibited in the non-aqueous secondary battery having the laminate for a non-aqueous secondary battery.

[0029] In addition, the present invention aims to advantageously solve the above problem. The method for manufacturing a laminate for a non-aqueous secondary battery according to the present invention comprises a process of supplying an adhesive material to at least one bonding surface among an electrode and a separator, and a process of bonding the electrode and the separator by applying pressure at room temperature through the bonding surface supplied with the adhesive material, wherein the adhesive material is formed using any one of the non-aqueous secondary battery adhesive layer compositions described above. In this way, by using an adhesive material obtained from any one of the non-aqueous secondary battery adhesive layer compositions described above, electrodes can be strongly bonded to each other at room temperature.

[0030] Meanwhile, in the present invention, "room temperature" refers to a temperature in the range of 25℃±5℃.

[0031] Furthermore, the present invention aims to advantageously solve the above problem, and the non-aqueous secondary battery of the present invention is characterized by having the laminate for a non-aqueous secondary battery described above. In this way, the non-aqueous secondary battery having the laminate for a non-aqueous secondary battery described above can exhibit excellent battery characteristics. Effects of the invention

[0032] According to the present invention, an adhesive layer for a non-aqueous secondary battery can be provided that secures inkjet ejection characteristics and can firmly bond battery components together under room temperature pressure, and a composition for an adhesive layer for a non-aqueous secondary battery can also be provided that exhibits excellent battery characteristics in a non-aqueous secondary battery.

[0033] In addition, according to the present invention, an adhesive layer for a non-aqueous secondary battery can be provided that firmly bonds battery members together by applying pressure at room temperature and also exhibits excellent electrical characteristics in the non-aqueous secondary battery.

[0034] In addition, according to the present invention, a laminate for a non-aqueous secondary battery can be provided that exhibits excellent electrical characteristics in a non-aqueous secondary battery.

[0035] In addition, according to the present invention, a non-aqueous secondary battery with excellent electrical characteristics can be provided.

[0036] In addition, according to the present invention, a method for manufacturing an adhesive layer for a non-aqueous secondary battery can be provided, which firmly bonds battery members together by applying pressure at room temperature and also enables excellent electrical characteristics for the non-aqueous secondary battery.

[0037] In addition, according to the present invention, a method for manufacturing a laminate for a non-aqueous secondary battery capable of exhibiting excellent electrical characteristics in a non-aqueous secondary battery can be provided. Brief explanation of the drawing

[0038] Figure 1 is a cross-sectional view schematically showing the structure of an example of a particulate polymer. FIG. 2 is a diagram illustrating an example of the manufacturing process of a laminate for a non-aqueous secondary battery according to the present invention. Figure 3 is a diagram illustrating the manufacturing process of a laminate for a non-aqueous secondary battery in the examples and comparative examples. Specific details for implementing the invention

[0039] Hereinafter, embodiments of the present invention will be described in detail.

[0040] Here, the composition for the adhesive layer of a non-aqueous secondary battery according to the present invention can be used when forming the adhesive layer for a non-aqueous secondary battery according to the present invention. The adhesive layer for a non-aqueous secondary battery according to the present invention can be manufactured, for example, by the method for manufacturing the adhesive layer for a non-aqueous secondary battery according to the present invention. The adhesive layer for a non-aqueous secondary battery according to the present invention can be used when manufacturing the laminate for a non-aqueous secondary battery according to the present invention and the non-aqueous secondary battery according to the present invention. The laminate for a non-aqueous secondary battery according to the present invention can be used when manufacturing the non-aqueous secondary battery according to the present invention and can be manufactured, for example, by the method for manufacturing the laminate for a non-aqueous secondary battery according to the present invention. Furthermore, the non-aqueous secondary battery according to the present invention comprises the laminate for a non-aqueous secondary battery according to the present invention.

[0041] (Composition for non-aqueous secondary battery adhesive layer)

[0042] The composition for a non-aqueous secondary battery adhesive layer of the present invention comprises a particulate polymer. The composition for a non-aqueous secondary battery adhesive layer of the present invention is typically a slurry composition formed by dispersing a particulate polymer in a solvent such as water, and may optionally include other components in addition to the particulate polymer.

[0043] In addition, the composition for a non-aqueous secondary battery adhesive layer of the present invention requires that the pressure sensitivity value of the adhesive force obtained by the following formula (1) be greater than 20 and less than 80.

[0044] Pressure sensitivity of adhesive force (N / (m·MPa)) = (T3 - T1) / 2···(1)

[0045] (In the formula, T1 represents the adhesion strength (N / m) of a polyethylene separator and an adhesive layer for a non-aqueous secondary battery obtained from a polyethylene separator and a composition for a non-aqueous secondary battery adhesive layer when the two layers are pressure-bonded at 25°C and a pressure of 1 MPa for 10 seconds, and T3 represents the adhesion strength (N / m) of a polyethylene separator and an adhesive layer for a non-aqueous secondary battery obtained from a polyethylene separator and a composition for a non-aqueous secondary battery adhesive layer when the two layers are pressure-bonded at 25°C and a pressure of 3 MPa for 10 seconds.)

[0046] The “pressure sensitivity of adhesive strength” obtained by the above formula (1) is the value obtained by dividing the difference (T3 - T1) between the adhesive strength T3 (N / m) when an adhesive layer for a non-aqueous secondary battery made using a polyethylene separator and a composition for a non-aqueous secondary battery is pressure-bonded at 25°C and a pressure of 3 MPa for 10 seconds, and the adhesive strength T1 (N / m) when an adhesive layer for a non-aqueous secondary battery obtained from a polyethylene separator and a composition for a non-aqueous secondary battery is pressure-bonded at 25°C and a pressure of 1 MPa for 10 seconds, by the difference (3 - 1 (= 2)) of the pressure (MPa) at each pressure bonding. That is, the pressure sensitivity of the adhesive force corresponds to the slope between a pressure of 1 MPa and 3 MPa on a graph in which the pressure at the time of bonding is plotted on the horizontal axis and the adhesive force on the vertical axis, and indicates the degree to which the adhesive force when bonded by applying a pressure of 3 MPa becomes greater than the adhesive force when bonded by applying a pressure of 1 MPa.

[0047] Furthermore, the composition for a non-aqueous secondary battery adhesive layer of the present invention has a pressure sensitivity value of adhesive strength greater than 20 and less than 80, thereby ensuring inkjet ejection characteristics while allowing for strong adhesion between battery components under room temperature pressure, and also enabling excellent battery characteristics in non-aqueous secondary batteries. If the above value is 20 or less, ejection by the inkjet method cannot be performed, or adhesive strength cannot be secured when attempting to adhere between battery components by room temperature pressure. On the other hand, if the above value is 80 or more, when adhesion is performed as a process and the durability of the battery is evaluated, the particulate polymer is deformed due to the influence of internal pressure generated by swelling of the battery, causing clogging of the separator, which increases the resistance of the secondary battery and deteriorates the battery characteristics.

[0048] Meanwhile, the “adhesive layer for non-aqueous secondary batteries” is a dried product of a composition for a non-aqueous secondary battery adhesive layer.

[0049] In addition, from the perspective of achieving high levels of inkjet ejection characteristics, adhesion between battery components when bonded by room temperature pressure, and battery characteristics of the secondary battery, the pressure sensitivity of the adhesive force is preferably 30 or higher, more preferably 40 or higher, even more preferably 45 or higher, preferably 70 or lower, and more preferably 60 or lower.

[0050] The pressure sensitivity of the adhesive force can be controlled, for example, by using a particulate polymer of a polymer alloy consisting of a polymer with a low glass transition temperature and a polymer with a high glass transition temperature, or by changing the glass transition temperature of the core part and the glass transition temperature of the shell part in a particulate polymer having a core-shell structure, and / or by changing the mass ratio of the shell part to the total of the core part and the shell part in a particulate polymer having a core-shell structure.

[0051] Particulate Polymer

[0052] The particulate polymer included in the composition for a non-aqueous secondary battery adhesive layer of the present invention is a component that functions as a binder in an adhesive layer (adhesive material) that bonds battery components such as separators or electrodes together. As for the particulate polymer used in the present invention, either a particulate polymer having a core-shell structure or a particulate polymer not having a core-shell structure may be used, but at least, it is preferable to use a particulate polymer having a core-shell structure.

[0053] <<Particulate polymer with core-shell structure>>

[0054] A particulate polymer having a core-shell structure has a core portion and a shell portion covering the outer surface of the core portion. By using a particulate polymer having a core-shell structure, it is easier to control the pressure sensitivity of the adhesion.

[0055] Here, the shell portion may cover the entire outer surface of the core portion or partially cover the outer surface of the core portion. On the other hand, even if it appears externally that the outer surface of the core portion is completely covered by the shell portion, if a hole is formed that communicates the inside and outside of the shell portion, that shell portion is a shell portion that partially covers the outer surface of the core portion.

[0056] Figure 1 shows an example cross-sectional structure of a particulate polymer. In Figure 1, the particulate polymer (300) has a core-shell structure comprising a core portion (310) and a shell portion (320). Here, the core portion (310) is a part of the particulate polymer (300) located further inside than the shell portion (320). Additionally, the shell portion (320) is a part that covers the outer surface (310S) of the core portion (310), and is typically the outermost part of the particulate polymer (300). Furthermore, in the example of Figure 1, the shell portion (320) does not cover the entire outer surface (310S) of the core portion (310), but rather partially covers the outer surface (310S) of the core portion (310).

[0057] Meanwhile, the particulate polymer may have any components other than the core and shell portions described above, as long as the desired effect is not significantly impaired. Specifically, for example, the particulate polymer may have a portion formed of a polymer different from the core portion inside the core portion. As a specific example, when the particulate polymer is manufactured by a seed polymerization method, the seed particles used may remain inside the core portion. However, from the perspective of significantly exhibiting the desired effect, it is preferable for the particulate polymer to have only the core and shell portions.

[0058] [Core]

[0059] -Glass transition temperature-

[0060] The glass transition temperature of the polymer in the core portion of the particulate polymer is preferably -50°C or higher, more preferably -45°C or higher, even more preferably -40°C or higher, preferably 25°C or lower, more preferably 10°C or lower, and even more preferably 0°C or lower. If the glass transition temperature of the polymer in the core portion is above the above lower limit, inkjet ejection characteristics can be improved. On the other hand, if the glass transition temperature of the polymer in the core portion is below the above upper limit, the polymer in the core portion can exhibit good adhesion, so that battery members can be bonded even more strongly to each other at room temperature pressure through an adhesive layer.

[0061] Meanwhile, the glass transition temperature of the polymer in the core part can be adjusted, for example, by changing the type or ratio of monomers used in the preparation of the polymer in the core part.

[0062] -furtherance-

[0063] Monomers used to prepare the polymer of the core portion include, for example, vinyl chloride-based monomers such as vinyl chloride and vinylidene chloride; vinyl acetate-based monomers such as vinyl acetate; aromatic vinyl monomers such as styrene, α-methylstyrene, styrenesulfonic acid, butoxystyrene, and vinylnaphthalene; vinylamine-based monomers such as vinylamine; vinylamide-based monomers such as N-vinylformamide and N-vinylacetamide; fluorine-free (meth)acrylic acid ester monomers such as methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, and cyclohexyl methacrylate; and (meth)acrylamide monomers such as acrylamide and methacrylamide. Examples include (meth)acrylonitrile monomers such as acrylonitrile and methacrylonitrile; fluorine-containing (meth)acrylic acid ester monomers such as 2-(perfluorohexyl)ethyl methacrylate and 2-(perfluorobutyl)ethyl acrylate; maleimide; maleimide derivatives such as phenylmaleimide. Additionally, one of these may be used alone, or two or more may be used in combination in any proportion.

[0064] Meanwhile, in the present invention, (meth)acrylic means acrylic and / or methacrylic, and (meth)acrylonitrile means acrylonitrile and / or methacrylonitrile.

[0065] Among these monomers, regarding the monomer used in the preparation of the polymer of the core portion, it is preferable to use at least a (meth)acrylic acid ester monomer in order to more strongly bond the battery members together through an adhesive layer; the combined use of a (meth)acrylic acid ester monomer and an aromatic vinyl monomer, or the combined use of a (meth)acrylic acid ester monomer and a (meth)acrylonitrile monomer, is more preferable, and the combined use of a (meth)acrylic acid ester monomer and an aromatic vinyl monomer is particularly preferable. That is, it is preferable that the polymer of the core portion contains at least a (meth)acrylic acid ester monomer unit; it is more preferable that it contains a (meth)acrylic acid ester monomer unit and an aromatic vinyl monomer unit or a (meth)acrylonitrile monomer unit; and it is even more preferable that it contains a (meth)acrylic acid ester monomer unit and an aromatic vinyl monomer unit.

[0066] Meanwhile, in the present invention, "comprising monomer units" means "a repeating unit derived from the monomer is included in the polymer obtained using the monomer."

[0067] In addition, in the present invention, "(meth)acrylic acid ester monomer" refers to a monofunctional (meth)acrylic acid ester monomer having only one polymerization reactive group.

[0068] In addition, regarding the view of further bonding the battery members together more firmly by interposing an adhesive material, the ratio of (meth)acrylic acid ester monomer units in the polymer of the core part is preferably 5 mass% or more, more preferably 10 mass% or more, particularly preferably 20 mass% or more, preferably 80 mass% or less, and more preferably 70 mass% or less.

[0069] In addition, when the polymer of the core part includes (meth)acrylic acid ester monomer units and aromatic vinyl monomer units, the proportion of aromatic vinyl monomer units in the polymer of the core part is preferably 15 mass% or more, more preferably 20 mass% or more, particularly preferably 25 mass% or more, preferably 95 mass% or less, more preferably 80 mass% or less, and particularly preferably 70 mass% or less, with respect to more strongly bonding the battery members together by interposing an adhesive material.

[0070] In addition, when the polymer of the core part includes (meth)acrylic acid ester monomer units and (meth)acrylonitrile monomer units, the ratio of (meth)acrylonitrile monomer units in the polymer of the core part is preferably 5 mass% or more, more preferably 10 mass% or more, particularly preferably 15 mass% or more, preferably 30 mass% or less, and more preferably 25 mass% or less, with respect to more strongly bonding the battery members together by interposing an adhesive material.

[0071] In addition, the polymer of the core portion may include an acid-containing monomer unit. Here, the acid-containing monomer may be a monomer having an acid group, for example, a monomer having a carboxylic acid group, a monomer having a sulfonic acid group, or a monomer having a phosphate group.

[0072] In addition, monomers having a carboxylic acid group include, for example, monocarboxylic acids and dicarboxylic acids. Examples of monocarboxylic acids include acrylic acid, methacrylic acid, and crotonic acid. Examples of dicarboxylic acids include maleic acid, fumaric acid, and itaconic acid.

[0073] In addition, monomers having a sulfonic acid group include, for example, vinylsulfonic acid, methylvinylsulfonic acid, (meth)allylsulfonic acid, (meth)acrylic acid-2-sulfonate ethyl, 2-acrylamido-2-methylpropanesulfonic acid, 3-allyloxy-2-hydroxypropanesulfonic acid, etc.

[0074] In addition, monomers having a phosphate group include, for example, phosphate-2-(meth)acryloyloxyethyl, methyl-2-(meth)acryloyloxyethyl, phosphate-(meth)acryloyloxyethyl, etc.

[0075] Meanwhile, in the present invention, (meth)allyl means allyl and / or metall, and (meth)acryloyl means acryloyl and / or methacryloyl.

[0076] Among these, as the acid-containing monomer, a monomer having a carboxylic acid group is preferred, and among them, a monocarboxylic acid is preferred, and (meth)acrylic acid is more preferred.

[0077] In addition, acid-containing monomers may be used as a single type, or two or more types may be combined in any ratio.

[0078] In addition, the ratio of acid-containing monomer units in the polymer of the core part is preferably 0.1 mass% or more, more preferably 1 mass% or more, more preferably 15 mass% or less, and more preferably 10 mass% or less, with the total repeating units (total monomer units) included in the polymer of the core part being 100 mass%. By making the ratio of acid-containing monomer units fall within the above range, the dispersibility of the polymer of the core part is increased when preparing the particulate polymer, making it easier to form a shell part that partially covers the outer surface of the polymer of the core part.

[0079] In addition, the polymer of the core portion preferably comprises crosslinkable monomer units in addition to the monomer units mentioned above. A crosslinkable monomer is a monomer capable of forming a crosslinked structure during or after polymerization by heating or irradiation with an energy beam.

[0080] Examples of crosslinkable monomers include polyfunctional monomers having two or more polymerizable reactive groups. Examples of such polyfunctional monomers include divinyl monomers such as divinylbenzene, 1,3-butadiene, isoprene, and allyl methacrylate; di(meth)acrylic acid ester monomers such as ethylene dimethacrylate, diethylene glycol dimethacrylate, ethylene glycol dimethacrylate, diethylene glycol diacrylate, and 1,3-butylene glycol diacrylate; tri(meth)acrylic acid ester monomers such as trimethylolpropane trimethacrylate and trimethylolpropane triacrylate; ethylenically unsaturated monomers containing epoxy groups such as allylglycidyl ether and glycidyl methacrylate; and γ-methacryloxypropyltrimethoxysilane. Among these, di(meth)acrylic acid ester monomers are more preferred. Additionally, one type may be used alone, or two or more types may be combined in any ratio.

[0081] In addition, the ratio of crosslinkable monomer units in the polymer of the core portion is preferably 0.1 mass% or more, more preferably 0.2 mass% or more, particularly preferably 0.4 mass% or more, preferably 10 mass% or less, more preferably 5 mass% or less, and particularly preferably 3 mass% or less, with the total repeating units (total monomer units) included in the polymer of the core portion being 100 mass%. By making the ratio of crosslinkable monomer units fall within the above range, the battery members can be bonded more strongly to each other through the interposition of an adhesive layer.

[0082] [Shellbu]

[0083] -Glass transition temperature-

[0084] The glass transition temperature of the polymer in the shell portion of the particulate polymer is preferably 50°C or higher, more preferably 53°C or higher, even more preferably 55°C or higher, particularly preferably 60°C or higher, preferably 200°C or lower, more preferably 120°C or lower, and even more preferably 105°C or lower. If the glass transition temperature of the polymer in the shell portion is above the lower limit, the inkjet ejection characteristics can be further improved. On the other hand, if the glass transition temperature of the polymer in the shell portion is below the upper limit, the particulate polymer becomes suitably flexible, so the battery members can be bonded more strongly to each other at room temperature through an adhesive layer.

[0085] The glass transition temperature of the polymer in the shell can be adjusted, for example, by changing the type or ratio of monomers used in the preparation of the polymer in the shell.

[0086] In addition, the glass transition temperature of the polymer in the shell portion is preferably 25°C or higher than the glass transition temperature of the polymer in the core portion described above, and more preferably 50°C or higher, in order to maintain the shape of the particulate polymer after bonding the battery members together and suppress the increase in resistance.

[0087] -furtherance-

[0088] As monomers used to prepare the polymer of the shell portion, for example, monomers identical to the monomers exemplified as monomers that can be used to prepare the polymer of the core portion may be used. In addition, one type of such monomer may be used alone, or two or more types may be used in combination in any ratio.

[0089] Among these monomers, regarding the monomer used in the preparation of the polymer of the shell portion, it is preferable to use at least one of a (meth)acrylic acid ester monomer and an aromatic vinyl monomer in order to bond the battery members more strongly together through an adhesive layer, and it is more preferable to use both the (meth)acrylic acid ester monomer and the aromatic vinyl monomer. That is, it is preferable for the polymer of the shell portion to include at least one of a (meth)acrylic acid ester monomer unit and an aromatic vinyl monomer unit, and it is more preferable for it to include both the (meth)acrylic acid ester monomer unit and the aromatic vinyl monomer unit.

[0090] In addition, regarding the view of further bonding the battery members more firmly together through the adhesive layer, the ratio of (meth)acrylic acid ester monomer units in the polymer of the shell part is preferably 10 mass% or more, more preferably 20 mass% or more, even more preferably 32.5 mass% or more, preferably 90 mass% or less, and more preferably 85 mass% or less, with the total repeating units (total monomer units) included in the polymer of the shell part being 100 mass%.

[0091] In addition, regarding the view of bonding the battery members more firmly together through the adhesive layer, the ratio of aromatic vinyl monomer units in the polymer of the shell part is preferably 50 mass% or more, more preferably 65 mass% or more, more preferably 99 mass% or less, and more preferably 95 mass% or less.

[0092] The polymer of the shell portion may include acid-containing monomer units in addition to (meth)acrylic acid ester monomer units and aromatic vinyl monomer units. Here, the acid-containing monomer may be a monomer having an acid group, for example, a monomer having a carboxylic acid group, a monomer having a sulfonic acid group, and a monomer having a phosphate group. Specifically, the acid-containing monomer may be the same monomer as the acid-containing monomer that can be used to form the core portion.

[0093] Among these, as the acid-containing monomer, a monomer having a carboxylic acid group is preferred, and among them, a monocarboxylic acid is more preferred, and (meth)acrylic acid is even more preferred.

[0094] In addition, acid-containing monomers may be used as a single type, or two or more types may be combined in any ratio.

[0095] In addition, the ratio of acid-containing monomer units in the polymer of the shell portion is preferably 0.1 mass% or more, more preferably 0.4 mass% or more, even more preferably 0.7 mass% or more, preferably 15 mass% or less, more preferably 10 mass% or less, and even more preferably 5 mass% or less, with the total repeating units (total monomer units) included in the polymer of the shell portion being 100 mass%. By making the ratio of acid-containing monomer units fall within the above range, the dispersibility of the particulate polymer is improved, and the battery members can be bonded even more strongly to each other through the interposition of the adhesive layer.

[0096] Here, the polymer of the shell portion may include hydroxyl group-containing monomer units.

[0097] As for hydroxyl-containing monomers capable of forming hydroxyl-containing monomer units of the polymer in the shell portion, monomers identical to the hydroxyl-containing monomers that can be used to form the core portion may be used.

[0098] In addition, the ratio of hydroxyl group-containing monomer units in the polymer of the shell portion is preferably 0.1 mass% or more, more preferably 0.4 mass% or more, even more preferably 0.7 mass% or more, preferably 15 mass% or less, more preferably 10 mass% or less, and even more preferably 5 mass% or less, with the total repeating units (total monomer units) included in the polymer of the shell portion being 100 mass%. By making the ratio of hydroxyl group-containing monomer units fall within the above range, the dispersibility of the particulate polymer is improved, and the battery members can be bonded even more strongly to each other through the interposition of the adhesive layer.

[0099] In addition, the polymer of the shell portion may include crosslinkable monomer units. Examples of crosslinkable monomers include the same monomers exemplified as crosslinkable monomers that can be used in the polymer of the core portion. Among these, di(meth)acrylic acid ester monomers and allyl methacrylate are preferred. In addition, one type of crosslinkable monomer may be used alone, or two or more types may be used in combination in any ratio.

[0100] In addition, the ratio of crosslinkable monomer units in the polymer of the shell portion is preferably 0.05 mass% or more, more preferably 0.1 mass% or more, even more preferably 0.2 mass% or more, preferably 4 mass% or less, more preferably 3 mass% or less, and even more preferably 2 mass% or less, with the total repeating units (total monomer units) included in the polymer of the shell portion being 100 mass%.

[0101] [Ratio of the shell's mass to the total mass of the core and shell]

[0102] A particulate polymer having a core-shell structure preferably has a mass ratio of the shell portion to the total of the core portion and the shell portion of 2 mass% or more, preferably 15 mass% or less, and more preferably 10 mass% or less. If the mass ratio of the shell portion is above the lower limit, the inkjet ejection characteristics can be further improved. In addition, if the mass ratio of the shell portion is below the upper limit, the battery members can be bonded more strongly to each other when pressurized at room temperature, and at the same time, the secondary battery can exhibit even better battery characteristics.

[0103] Here, the mass ratio of the shell portion to the total of the core portion and the shell portion is determined from the ratio of the thickness of the core portion and the shell portion described later and the specific gravity of the particulate polymer.

[0104] [Volume average particle size of particulate polymers with a core-shell structure]

[0105] The volume average particle size of the particulate polymer having a core-shell structure is preferably 100 nm or more, more preferably 200 nm or more, preferably 1500 nm or less, more preferably 900 nm or less, even more preferably 800 nm or less, and even more preferably 700 nm or less. If the volume average particle size of the particulate polymer having a core-shell structure is 100 nm or more, the deterioration of battery characteristics caused by an increase in resistance of the secondary battery due to hindering the lithium ion path of the substrate (electrode or separator) can be suppressed. In addition, if the volume average particle size is 1500 nm or less, clogging of the nozzle can be further suppressed when the composition for a non-aqueous secondary battery adhesive layer is coated by an inkjet method, thereby improving inkjet ejection characteristics.

[0106] [Ratio of average shell thickness to volume average particle size]

[0107] The ratio of the average thickness of the shell portion to the volume average particle size of a particulate polymer having a core-shell structure is preferably 0.1% or more, more preferably 0.5% or more, preferably 15% or less, and more preferably 10% or less. If the average thickness of the shell portion is above the lower limit, the inkjet ejection characteristics can be further improved. In addition, if the average thickness of the shell portion is below the upper limit, the battery members can be bonded more strongly to each other when the battery members are pressurized at room temperature.

[0108] Here, the average thickness of the shell portion of a particulate polymer having a core-shell structure is determined by observing the cross-sectional structure of the particulate polymer having a core-shell structure using a transmission electron microscope (TEM). Specifically, the maximum thickness of the shell portion in the cross-sectional structure of the particulate polymer is measured using TEM, and the average value of the maximum thickness of the shell portion of at least 20 arbitrarily selected particulate polymer particles is taken as the average thickness of the shell portion. However, if the shell portion is composed of polymer particles, and furthermore, in the diameter direction of the particulate polymer particles, the particles constituting the shell portion do not overlap with each other and the polymer particles form the shell portion as a single layer, the number average particle diameter of the particles constituting the shell portion is taken as the average thickness of the shell portion.

[0109] [Method for preparing a particulate polymer having a core-shell structure]

[0110] In addition, the particulate polymer having the core-shell structure described above can be prepared, for example, by using a monomer of the polymer in the core portion and a monomer of the polymer in the shell portion, and polymerizing in stages while changing the ratio of the monomers over time. Specifically, the particulate polymer can be prepared by a continuous multi-stage emulsion polymerization method and a multi-stage suspension polymerization method in which the polymer of the preceding stage is sequentially coated by the polymer of the subsequent stage.

[0111] Accordingly, an example of obtaining a particulate polymer having the above-mentioned core-shell structure by a multi-stage emulsion polymerization method is presented below.

[0112] In polymerization, according to conventional methods, anionic surfactants such as sodium dodecylbenzenesulfonate and sodium dodecyl sulfate, nonionic surfactants such as polyoxyethylene nonylphenyl ether and sorbitan monolaurate, or cationic surfactants such as octadecylamine acetate may be used as emulsifiers. In addition, as polymerization initiators, peroxides such as t-butylperoxy-2-ethylhexanoate, potassium persulfate, and cumene peroxide, or azo compounds such as 2,2'-azobis(2-methyl-N-(2-hydroxyethyl)-propionamide) and 2,2'-azobis(2-amidinopropane) hydrochloride may be used.

[0113] In addition, regarding the polymerization sequence, first, a monomer forming the core part and an emulsifier are mixed, and a particulate polymer constituting the core part is obtained by carrying out emulsion polymerization in batches. Furthermore, by performing polymerization of a monomer forming the shell part in the presence of the particulate polymer constituting the core part, a particulate polymer having the above-described core-shell structure can be obtained.

[0114] In this case, when preparing a particulate polymer that partially covers the outer surface of the core part by the shell part, it is preferable to divide the monomer forming the polymer of the shell part into multiple stages or supply it to the polymerization system continuously. By dividing or continuously supplying the monomer forming the polymer of the shell part to the polymerization system, the polymer constituting the shell part is formed in a particulate form, and by combining this particle with the core part, a shell part that partially covers the core part can be formed.

[0115] <<Particulate polymer without core-shell structure>>

[0116] [Glass transition temperature]

[0117] Here, the glass transition temperature of the particulate polymer not having a core-shell structure is preferably -40°C or higher, more preferably -35°C or higher, even more preferably -30°C or higher, preferably 0°C or lower, more preferably -10°C or lower, and even more preferably -20°C or lower. If the glass transition temperature of the particulate polymer not having a core-shell structure is -40°C or higher, the battery members can be bonded more strongly to each other by interposing an adhesive material. On the other hand, if the glass transition temperature of the particulate polymer not having a core-shell structure is 0°C or lower, the detachment of the particulate polymer from the substrate can be suppressed.

[0118] [furtherance]

[0119] As monomers used to prepare particulate polymers that do not have a core-shell structure, monomers identical to the monomers exemplified as monomers that can be used to prepare the polymer of the core portion of the particulate polymer having the core-shell structure described above may be used. For example, as monomers used to prepare particulate polymers that do not have a core-shell structure, it is preferable to use (meth)acrylic acid ester monomers, aromatic vinyl monomers, acid group-containing monomers, and crosslinkable monomers. Meanwhile, one type of such monomer may be used alone, or two or more types may be used in combination in any ratio.

[0120] In particulate polymers that do not have a core-shell structure, the ratio of (meth)acrylic acid ester monomer units is preferably 40 mass% or more, more preferably 50 mass% or more, more preferably 60 mass% or more, more preferably 85 mass% or less, more preferably 80 mass% or less, and more preferably 75 mass% or less, with respect to more strongly bonding battery members together through an adhesive layer.

[0121] In particulate polymers that do not have a core-shell structure, the ratio of aromatic vinyl monomer units is preferably 10 mass% or more, more preferably 15 mass% or more, more preferably 20 mass% or more, more preferably 40 mass% or less, more preferably 35 mass% or less, and more preferably 30 mass% or less, with respect to more strongly bonding battery members together through an adhesive layer.

[0122] In a particulate polymer that does not have a core-shell structure, the ratio of an acid-containing monomer unit is preferably 0.5 mass% or more, more preferably 1 mass% or more, even more preferably 2 mass% or more, preferably 10 mass% or less, more preferably 7 mass% or less, and even more preferably 5 mass% or less, with the total repeating unit (total monomer unit) included in the polymer being 100 mass%. By making the ratio of an acid-containing monomer unit in a particulate polymer that does not have a core-shell structure fall within the above range, the dispersibility of the particulate polymer can be improved.

[0123] In particulate polymers that do not have a core-shell structure, the ratio of crosslinkable monomer units is preferably 0.2 mass% or more, more preferably 0.5 mass% or more, more preferably 1 mass% or more, more preferably 5 mass% or less, more preferably 4 mass% or less, and more preferably 3 mass% or less, with respect to more strongly bonding battery members together through an adhesive layer.

[0124] [Volume average particle size of particulate polymers without a core-shell structure]

[0125] The volume average particle size of the particulate polymer not having a core-shell structure is preferably 50 nm or more, more preferably 100 nm or more, even more preferably 200 nm or more, preferably 600 nm or less, more preferably 500 nm or less, and even more preferably 400 nm or less. If the volume average particle size of the particulate polymer not having a core-shell structure is within the above predetermined range, the battery members can be bonded more strongly to each other by interposing an adhesive material.

[0126] [Content of particulate polymers without a core-shell structure]

[0127] The content of particulate polymers not having a core-shell structure in the composition for the adhesive layer can be appropriately adjusted within the range in which the desired effect of the present invention is obtained. It is preferable that the content be 5 parts by mass or more, and more preferable that it be 10 parts by mass or more, per 100 parts by mass of particulate polymers having a core-shell structure. If the content of particulate polymers not having a core-shell structure is above the above lower limit, the detachment of particulate polymers from the substrate can be suppressed.

[0128] [Method for manufacturing particulate polymers without a core-shell structure]

[0129] Particulate polymers that do not have a core-shell structure are not particularly limited and, for example, can be prepared by polymerizing a monomer composition containing the monomers described above in an aqueous solvent such as water. Here, the ratio of each monomer in the monomer composition is typically equal to the ratio of each monomer unit in the particulate polymer that does not have a core-shell structure. Furthermore, the polymerization method and polymerization reaction are not particularly limited and known polymerization methods and polymerization reactions may be used.

[0130] <<Electrolyte Swelling Degree>>

[0131] The degree of swelling of the particulate polymer in the electrolyte (a solution in which LiPF6 is dissolved at a concentration of 1 mol / L in a mixed solvent with a volume ratio of ethylene carbonate / diethyl carbonate = 3 / 7) (hereinafter referred to simply as "degree of swelling") is not specifically defined in a range, but it is preferable that it not dissolve in the electrolyte. If it dissolves, there is a concern that the battery characteristics will deteriorate.

[0132] Meanwhile, the degree of swelling of the particulate polymer with respect to the electrolyte can be measured by the method described in the examples of this specification.

[0133] <Solvent>

[0134] The solvent for dispersing the above particulate polymer is not particularly limited, and for example, water, organic solvents, and mixtures thereof may be used. Meanwhile, organic solvents are not particularly limited and may include cyclic aliphatic hydrocarbons such as cyclopentane and cyclohexane; aromatic hydrocarbons such as toluene and xylene; ketones such as ethylmethyl ketone and cyclohexanone; esters such as ethyl acetate, butyl acetate, γ-butyrolactone and ε-caprolactone; nitriles such as acetonitrile and propionitrile; ethers such as tetrahydrofuran and ethylene glycol diethyl ether; and alcohols such as methanol, ethanol, isopropanol, ethylene glycol, propylene glycol, and ethylene glycol monomethyl ether.

[0135] Among the above, it is desirable to use water from the perspective of simplifying the equipment.

[0136] At least a portion of the aforementioned solvent may be removed by drying or the like during the manufacturing process of a laminate for a non-aqueous secondary battery.

[0137] Other ingredients

[0138] Other components optionally included in the composition for a non-aqueous secondary battery adhesive layer of the present invention are not particularly limited and may include, for example, a surface tension modifier, a dispersant different from the dispersant used in the polymerization, a viscosity modifier, a reinforcing agent, an electrolyte additive, etc. These are not particularly limited as long as they do not affect the battery reaction, and known ones, for example, those described in International Publication No. 2012 / 115096, may be used. Meanwhile, one type of these components may be used alone, or two or more types may be used in combination in any ratio.

[0139] Method for preparing a composition for a non-aqueous secondary battery adhesive layer

[0140] The method for preparing the composition for a non-aqueous secondary battery adhesive layer according to the present invention is not particularly limited and, for example, can be prepared by stirring and mixing a particulate polymer and any other component in the presence of a solvent. Here, the stirring and mixing method is not particularly limited and can be performed by known methods. Specifically, a general stirring vessel, ball mill, sand mill, bead mill, pigment disperser, ultrasonic disperser, blast furnace, homogenizer, planetary mixer, fill mixer, etc., can be used. The mixing conditions are not particularly limited, but typically, the mixing can be performed for 10 minutes or more and several hours or less in a range of room temperature or higher and 80°C or lower.

[0141] (Adhesive layer for non-aqueous secondary batteries)

[0142] The adhesive layer for a non-aqueous secondary battery according to the present invention is obtained by using the composition for the adhesive layer of a non-aqueous secondary battery according to the present invention. Furthermore, the adhesive layer for a non-aqueous secondary battery according to the present invention functions as an adhesive material for bonding battery components used in a non-aqueous secondary battery. In addition, the adhesive layer for a non-aqueous secondary battery according to the present invention can be obtained, for example, by the method for manufacturing the adhesive layer for a non-aqueous secondary battery according to the present invention described below.

[0143] Here, the adhesive layer for a non-aqueous secondary battery according to the present invention is a dried product formed by drying the composition for an adhesive layer for a non-aqueous secondary battery according to the present invention. Accordingly, the adhesive layer for a non-aqueous secondary battery according to the present invention comprises at least the particulate polymer described above and optionally comprises other components described above.

[0144] In addition, the particulate polymer exists in a particulate form in the composition for the non-aqueous secondary battery adhesive layer, but in the adhesive layer for the non-aqueous secondary battery, it may be in a particulate form or any other shape.

[0145] The shape of the adhesive layer is not particularly limited and can be formed into any planar shape, such as a stripe shape, a dot shape, or a grid shape. Among these, from the perspective of reducing the resistance of the secondary battery, it is preferable to form the adhesive layer in a dot shape. A dot-shaped adhesive layer can be obtained by an inkjet method using, for example, the coating machine (51 to 54 in FIG. 2) described later.

[0146] The diameter of the dots in the adhesive layer arranged in a dot pattern is preferably 10 μm or more, more preferably 20 μm or more, preferably 300 μm or less, and more preferably 200 μm or less. If the diameter of the dots in the adhesive layer is greater than or equal to the lower limit, the adhesion strength between the electrode and the separator can be increased. On the other hand, if the diameter of the dots in the adhesive layer is less than or equal to the upper limit, the degradation of the output characteristics of the secondary battery can be suppressed.

[0147] It is preferable that the thickness of the dots of the adhesive layer arranged in a dot pattern be 5 μm or more. If the thickness of the dots of the adhesive layer is greater than or equal to the lower limit above, the adhesion between the electrode and the separator can be increased.

[0148] In addition, the mass per unit area of ​​the adhesive layer is 0.02 g / m² 2 It is desirable that it be above 1.0 g / m² 2 It is desirable that it be less than or equal to 0.35 g / m²2 It is more preferable that it be below. If the mass per unit area of ​​the adhesive layer is above the above lower limit, sufficient adhesion between the electrode and the separator can be secured. In addition, if the mass per unit area of ​​the adhesive layer is below the above upper limit, sufficiently high output characteristics of the secondary battery can be secured.

[0149] In addition, the coverage rate of the adhesive layer is preferably 1% or more, more preferably 5% or more, preferably 50% or less, and more preferably 30% or less. If the coverage rate of the adhesive layer is above the lower limit, the adhesion between the electrode and the separator can be secured. In addition, if the coverage rate of the adhesive layer is below the upper limit, the output characteristics of the secondary battery can be secured sufficiently high.

[0150] Here, the “coverage rate of the adhesive layer” in any surface or area refers to the ratio of the area of ​​the portion covered by the adhesive layer to the total area of ​​the surface or area [(area of ​​the portion covered by the adhesive layer / total area of ​​the surface or area) × 100 (%)].

[0151] Meanwhile, when an adhesive layer composition comprising a particulate polymer and a solvent is used, the "adhesive layer" in the "coverage rate of the adhesive layer" refers to the dried product of the adhesive layer composition.

[0152] The coverage rate of the adhesive layer can be adjusted by changing the arrangement pattern of the adhesive layer placed (coated) in each area. Specifically, in an area where the adhesive layer is arranged (coated) in a dot pattern, the coverage rate of the adhesive layer in that area can be adjusted by changing the radius and the distance between the centers of the adhesive layer dots. For example, in an area where the adhesive layer is placed (coated) in a dot pattern formed by dots being formed at regular intervals in two orthogonal directions, the coverage rate of the adhesive layer can be calculated by the following equation (2) using the distance (pitch) x and y between the centers of the dots and the radius r of the dots.

[0153] Coverage rate of the adhesive layer = {πr 2 / (x·y)} × 100(%)···(2)

[0154] (Method for manufacturing an adhesive layer for non-aqueous secondary batteries)

[0155] The method for manufacturing an adhesive layer for a non-aqueous secondary battery according to the present invention comprises a process of coating the composition for the adhesive layer for a non-aqueous secondary battery according to the present invention onto the surface of a substrate by an inkjet method (coating process), and a process of drying the composition for the adhesive layer for a non-aqueous secondary battery coated on the substrate (drying process). Additionally, the method for manufacturing an adhesive layer for a non-aqueous secondary battery according to the present invention may include a process of peeling off the adhesive layer for a non-aqueous secondary battery formed on the substrate after the drying process (peeling process).

[0156] Here, when an adhesive layer for a non-aqueous secondary battery is formed on an electrode substrate or a separator substrate as a substrate, the electrode substrate and the separator substrate can be laminated as is to form a laminate. In addition, when an adhesive layer for a non-aqueous secondary battery is formed on a release substrate as a substrate, after peeling off the adhesive layer for a non-aqueous secondary battery from the release agent, it can be used for bonding the electrode substrate and the separator substrate.

[0157] Coating Process

[0158] In the coating process, droplets of the composition for a non-aqueous secondary battery adhesive layer according to the present invention are coated onto a substrate such as an electrode substrate, a separator substrate, or a release substrate through the nozzle of an inkjet coating machine. A conventionally known inkjet coating machine may be used, and for example, coating may be performed using a coating machine (51 to 54 in FIG. 2) described below. From the perspective of manufacturing efficiency, it is preferable to coat the composition for a non-aqueous secondary battery adhesive layer onto an electrode substrate or a separator substrate, and from the perspective of facilitating the drying process, it is preferable to coat the composition for a non-aqueous secondary battery adhesive layer onto an electrode substrate.

[0159] The coating conditions by the inkjet method are not particularly limited as long as the composition for the non-aqueous secondary battery adhesive layer can be coated on the substrate, and can be appropriately adjusted according to the desired shape of the resulting adhesive layer (shape in planar form, diameter of the dots, thickness of the dots, pitch of the dots, coverage rate, mass per unit area, etc.).

[0160] <<Electrode Substrate>>

[0161] As for the electrode substrate, known electrode substrates may be used without being particularly limited. For example, as the electrode substrate, an electrode comprising an electrode substrate formed by forming an electrode composite layer on one or both sides of a current collector, or an electrode comprising an electrode substrate further formed by forming a porous film layer on the electrode composite layer of the electrode substrate may be used.

[0162] Meanwhile, the current collector, electrode composite layer, and porous film layer are not particularly limited, and any current collector, electrode composite layer, and porous film layer that can be used in the field of secondary batteries, such as those described in Japanese Patent Publication No. 2013-145763, may be used.

[0163] <<Separator included>>

[0164] The separator substrate is not particularly limited, and known separator substrates, such as organic separator substrates, may be used. An organic separator substrate is a porous member made of an organic material. Examples of organic separator substrates include microporous membranes or nonwoven fabrics comprising polyolefin resins such as polyethylene and polypropylene, or aromatic polyamide resins; a microporous membrane or nonwoven fabric made of polyethylene is preferred due to its excellent strength. Additionally, from the perspective of safety, a heat-resistant separator coated with ceramic on the separator is preferred.

[0165] In addition, the separator substrate may have a porous membrane layer formed on one side or both sides. A porous membrane layer refers to a layer containing non-conductive particles, such as that described in, for example, Japanese Patent Publication No. 2013-145763.

[0166] <<Heterogeneous Entry>>

[0167] As for the type of material, it is not particularly limited and known materials may be used.

[0168] Drying Process

[0169] In the drying process, the composition for the adhesive layer coated on the substrate is dried to form an adhesive layer on the substrate consisting of the dried product of the composition for the adhesive layer. The drying method is not particularly limited and any known method may be used. Examples of drying methods include drying methods using heating devices such as heaters, dryers, and heat rollers. The drying conditions are not particularly limited, but the drying temperature is preferably 50°C or higher and 90°C or lower, and the drying time is preferably 1 second or higher and 120 seconds or lower.

[0170] <Peeling Process>

[0171] In the peeling process, the adhesive layer for a non-aqueous secondary battery formed on the substrate is peeled off. When the adhesive layer for a non-aqueous secondary battery is formed on a release substrate, the adhesive layer can be peeled off from the release substrate and provided, for example, for the manufacture of a laminate for a non-aqueous secondary battery described later.

[0172] (Laminate for non-aqueous secondary batteries)

[0173] The laminate for a non-aqueous secondary battery according to the present invention is a laminate for a non-aqueous secondary battery having an electrode and a separator, wherein the electrode and the separator are bonded together via the adhesive layer for a non-aqueous secondary battery according to the present invention described above. Here, the electrode that is bonded to the separator to form the laminate for a non-aqueous secondary battery may be only a positive electrode, only a negative electrode, or both a positive electrode and a negative electrode. Furthermore, when a laminate for a non-aqueous secondary battery is obtained by bonding both a positive electrode and a negative electrode to a separator, the number of positive electrodes, negative electrodes, and separators in the laminate for a non-aqueous secondary battery may each be one or two or more. That is, the structure of the laminate for a non-aqueous secondary battery according to the present invention may be any of the following (1) to (6).

[0174] (1) Positive / Separator

[0175] (2) Negative electrode / separator

[0176] (3) Positive / Separator / Negative

[0177] (4) Positive / Separator / Negative / Separator

[0178] (5) Separator / Positive / Separator / Negative

[0179] (6) A structure in which multiple positive and negative poles are alternately stacked with a separator in between (e.g., "separator / negative pole / separator / positive pole / separator / negative pole····· / separator / positive pole")

[0180] Electrode

[0181] As for the electrode, there are no particular limitations, and known electrodes may be used; for example, those described in the section "Method for manufacturing an adhesive layer for a non-aqueous secondary battery" may be used.

[0182] Separator

[0183] As for the separator, there are no particular limitations, and known separators may be used; for example, those described in the section "Method for manufacturing an adhesive layer for a non-aqueous secondary battery" may be used.

[0184] <Adhesive layer>

[0185] The adhesive layer bonding the electrode and the separator is, as described above, a dried product of the composition for a non-aqueous secondary battery adhesive layer according to the present invention. That is, the dried product comprises at least a polymer derived from a particulate polymer, and optionally comprises other components described above.

[0186] In addition, the preferred shape of the adhesive layer (dot diameter, dot thickness, dot pitch, coverage rate, mass per unit area, etc.) is the same as that described in the section <Adhesive layer for non-aqueous secondary batteries>.

[0187] In addition, the particulate polymer exists in a particulate form in the composition for the non-aqueous secondary battery adhesive layer, but in the adhesive layer for the non-aqueous secondary battery in the laminate, it may be in a particulate form or any other shape.

[0188] (Method for manufacturing a laminate for a non-aqueous secondary battery)

[0189] The method for manufacturing a laminate for a non-aqueous secondary battery according to the present invention comprises a process of supplying an adhesive material to a bonding surface (i.e., a surface forming an adhesive material (adhesive layer)) of at least one of an electrode and a separator (supply process), and a process of bonding the electrode and the separator by applying pressure at room temperature through the bonding surface to which the adhesive material was supplied (bonding process). Additionally, the method for manufacturing a laminate for a non-aqueous secondary battery according to the present invention may include a process of cutting the obtained laminate after the bonding process (cutting process).

[0190] Supply Process

[0191] In the supply process, an adhesive material is supplied to the bonding surface of at least one of the electrode (positive electrode, negative electrode) and the separator. The supply of the adhesive material can be performed by coating the composition for a non-aqueous secondary battery adhesive layer of the present invention by an inkjet method and drying it. Alternatively, the supply of the adhesive material may be performed by transferring (laminating) the adhesive layer for a non-aqueous secondary battery obtained by peeling from a release substrate as described above onto the bonding surface.

[0192] The conditions of the inkjet method are not particularly limited as long as the composition for the non-aqueous secondary battery adhesive layer can be coated, and can be appropriately adjusted according to the desired shape of the resulting adhesive material (shape in planar form, diameter of the dots, thickness of the dots, pitch of the dots, coverage rate, mass per unit area, etc.).

[0193] When a composition for a non-aqueous secondary battery adhesive layer is coated by an inkjet method, the composition for the non-aqueous secondary battery adhesive layer can be dried while transporting the electrode and separator to the bonding start position without contacting another member to the bonding surface to which the composition for the non-aqueous secondary battery adhesive layer is supplied. If no other member is contacted to the bonding surface to which the composition for the non-aqueous secondary battery adhesive layer is supplied, problems such as blocking do not occur, so a laminate for a secondary battery can be manufactured efficiently. When supplying an adhesive layer for a non-aqueous secondary battery obtained by peeling from a release substrate, drying may not be performed.

[0194] Meanwhile, in the present invention, "joining start position" refers to a position in which the joining surface of the electrode and the joining surface of the separator come into contact with each other during the joining of the electrode and the separator.

[0195] The conveying of the electrode and separator is not particularly limited and can be performed using any conveying mechanism, such as a roller, belt conveyor, manipulator, or adsorption band. Among these, from the perspective of further increasing the manufacturing efficiency of a laminate for a secondary battery, it is preferable to convey at least one of the electrode and separator using a roller.

[0196] In addition, the drying of the composition for the non-aqueous secondary battery adhesive layer is not particularly limited and can be performed using a heating device such as a heater, dryer, or heat roller. The temperature during drying of the electrode and / or separator supplied with the composition for the non-aqueous secondary battery adhesive layer is not particularly limited, but is preferably 50°C or higher and 90°C or lower. In addition, the drying time is not particularly limited, but is preferably 1 second or higher and 120 seconds or lower.

[0197] <Joining Process>

[0198] In the bonding process, the electrode and the separator are bonded through a bonding surface. The bonding is performed by applying pressure at room temperature to a laminate of the electrode and the separator that are overlapped through the bonding surface.

[0199] The pressure when pressurizing the laminate can be appropriately adjusted depending on the type and amount of particulate polymer used, but it is preferable to be greater than 1 MPa and less than or equal to 5 MPa.

[0200] <Cutting Process>

[0201] The cutting process is a process of cutting the laminate obtained from the bonding process to a desired size. For cutting, any cutting machine that can be used in the field of manufacturing secondary batteries may be used, such as a cutting machine that cuts the laminate by inserting cutting blades from both sides in the thickness direction of the laminate.

[0202] <<Electrode and Separator>>

[0203] As for the electrode and separator, known electrodes and separators may be used without being particularly limited. For example, the electrode and separator described above in the section "Method for manufacturing an adhesive layer for a non-aqueous secondary battery" may be used.

[0204] <<Adhesive Material>>

[0205] The adhesive material for bonding the electrode and the separator is a dried product of the composition for a non-aqueous secondary battery adhesive layer according to the present invention. That is, the dried product comprises at least a polymer derived from a particulate polymer, and optionally comprises other components as described above.

[0206] In addition, the preferred form of the adhesive material (dot diameter, dot thickness, dot pitch, coverage rate, mass per unit area, etc.) is the same as that described in the section <Adhesive layer for non-aqueous secondary batteries>.

[0207] In addition, the particulate polymer exists in a particulate form in the composition for the non-aqueous secondary battery adhesive layer, but in the adhesive layer for the non-aqueous secondary battery in the laminate after pressurization, it may be in a particulate form or any other shape.

[0208] Hereinafter, an example of the manufacturing process of a laminate for a non-aqueous secondary battery according to the present invention will be explained with reference to FIG. 2.

[0209] Referring to FIG. 2, a long first separator fabric (10A) unwound from a first separator fabric roll is laminated to one side of a negative material consisting of a long negative fabric (20A) unwound from a negative fabric roll, with an adhesive material supplied from a coating machine (51) interposed therebetween. At the same time, a long second separator fabric (30A) unwound from a second separator fabric roll is laminated to the other side of the negative material consisting of the negative fabric (20A), with an adhesive material supplied from a coating machine (52) interposed therebetween. Meanwhile, lamination can be performed, for example, using compression rollers (61, 62). Then, an adhesive material supplied from a coating machine (53) is interposed on the surface opposite to the negative electrode fabric (20A) side of the first separator fabric (10A), and a positive electrode (40) is laminated at a predetermined arrangement pitch to obtain a laminated body having a positive electrode. Meanwhile, in FIG. 2, an adhesive material is supplied from a coating machine (54) to the surface opposite to the negative electrode fabric (20A) side of the second separator fabric (30A), so that when a laminate obtained by cutting the laminate between positive electrodes (40) adjacent in the longitudinal direction is overlapped to produce an overlapping body, the laminates can be bonded well to each other. Then, a cutting machine (70) is used to cut the laminate to obtain a laminate.

[0210] (Non-aqueous secondary battery)

[0211] The non-aqueous secondary battery of the present invention comprises a laminate for the non-aqueous secondary battery of the present invention. The non-aqueous secondary battery of the present invention comprises, for example, electrodes (positive electrode and negative electrode), an electrolyte, and a separator. At least one of the positive electrode and the negative electrode and the separator are laminated together via an adhesive layer for the non-aqueous secondary battery of the present invention to form a laminate for the non-aqueous secondary battery of the present invention. Since the non-aqueous secondary battery of the present invention comprises a laminate for the non-aqueous secondary battery of the present invention, it can exhibit excellent battery characteristics.

[0212] Electrode

[0213] The electrode used in the secondary battery of the present invention is not limited to known electrodes, and for example, the one described in the claim "Method for manufacturing an adhesive layer for a non-aqueous secondary battery" may be used.

[0214] Separator

[0215] The separator used in the secondary battery of the present invention is not limited to any known separator, and for example, the one described in the claim "Method for manufacturing an adhesive layer for a non-aqueous secondary battery" may be used.

[0216] Electrolyte

[0217] Typically, an organic electrolyte is used in which a supporting electrolyte is dissolved in an organic solvent as the electrolyte used in the secondary battery of the present invention. For example, when the non-aqueous secondary battery is a lithium-ion secondary battery, a lithium salt is used as the supporting electrolyte. Examples of lithium salts include LiPF6, LiAsF6, LiBF4, LiSbF6, LiAlCl4, LiClO4, CF3SO3Li, C4F9SO3Li, CF3COOLi, (CF3CO)2NLi, (CF3SO2)2NLi, (C2F5SO2)NLi, etc. Among these, LiPF6, LiClO4, and CF3SO3Li are preferred because they are easily soluble in a solvent and exhibit a high degree of dissociation, and LiPF6 is particularly preferred. Meanwhile, the electrolyte may be used as a single type or two or more types may be used in combination in any ratio. Typically, lithium ion conductivity tends to increase as the degree of dissociation of the supporting electrolyte used increases, so lithium ion conductivity can be controlled by the type of supporting electrolyte.

[0218] In addition, the organic solvent used in the electrolyte is not particularly limited as long as it is capable of dissolving the supporting electrolyte, but for example, carbonates such as dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), butylene carbonate (BC), and ethyl methyl carbonate (EMC); esters such as γ-butyrolactone and methyl formate; ethers such as 1,2-dimethoxyethane and tetrahydrofuran; and sulfur-containing compounds such as sulfolane and dimethyl sulfoxide are suitably used. In addition, a mixture of these solvents may be used. Among these, it is preferable to use carbonates because they have a high dielectric constant and a wide stable potential range, and it is even more preferable to use a mixture of ethylene carbonate and ethyl methyl carbonate.

[0219] In addition, known additives, such as vinylene carbonate (VC), fluoroethylene carbonate (FEC) or ethylmethylsulfone, may be added to the electrolyte.

[0220] (Method for manufacturing a secondary battery)

[0221] The secondary battery of the present invention can be manufactured, for example, by placing a stacked body obtained by stacking a laminate, which is then wound or folded according to the battery shape as needed, into a device container (battery container), and injecting an electrolyte into the device container to seal it. Meanwhile, the stacked body may be the laminate itself, or it may be manufactured by stacking multiple laminates. Additionally, the stacked body may be manufactured by stacking an additional battery component (electrode and / or separator, etc.) with the laminate. Furthermore, in order to prevent the occurrence of internal pressure rise, overcharge / discharge, etc., the secondary battery of the present invention may be equipped with an overcurrent protection element such as a fuse or PTC element, expanded metal, lead plate, etc., as needed. The shape of the secondary battery may be any of the following: for example, coin type, button type, sheet type, cylindrical type, prismatic type, flat type, etc.

[0222] Examples

[0223] The present invention will be described in detail below based on examples, but the present invention is not limited to these examples. Meanwhile, in the following description, "%" and "parts" indicating amounts are based on mass unless otherwise specified.

[0224] In addition, in a polymer produced by copolymerizing multiple types of monomers, the proportion of a monomer unit formed by polymerizing a certain monomer in the polymer is, unless otherwise noted, usually equal to the proportion (input ratio) of that monomer in the total monomers used in the polymerization of the polymer.

[0225] Various measurements and evaluations in the examples and comparative examples were performed by the following methods.

[0226] Glass transition temperature

[0227] An aqueous dispersion of the particulate polymer prepared in each preparation example was dried at a temperature of 130°C for 1 hour to be used as a sample. 10 mg of the measurement sample was weighed into an aluminum pan, and a differential scanning calorimetry (DSC) curve was obtained by performing measurements using a differential thermal analysis device ("EXSTAR DSC6220" manufactured by SI Nanotechnologies Co., Ltd.) under conditions specified in JIS Z8703, with a heating rate of 10°C / min and a measurement temperature range between -100°C and 200°C. Meanwhile, an empty aluminum pan was used as a reference. During this heating process, the intersection point between the baseline immediately before the endothermic peak of the DSC curve, where the differential signal (DDSC) is 0.05 mW / min / mg or higher, and the tangent of the DSC curve at the inflection point that first appears after the endothermic peak, was determined as the glass transition temperature (°C).

[0228] Volume average particle size

[0229] The volume average particle size of the particulate polymer prepared in each preparation example was measured by laser diffraction. Specifically, a water dispersion solution (solid content concentration 0.1 mass%) containing the prepared particulate polymer was used as a sample, and the particle size distribution (based on volume) obtained by a laser diffraction particle size distribution measuring device (manufactured by Beckmann Coulter, product name "LS-13 320") was determined as the particle size at which the cumulative volume calculated from the small diameter side becomes 50%, and the volume average particle size was set to D50 (nm).

[0230] <Electrolyte Swelling Degree>

[0231] The aqueous dispersion of the particulate polymer prepared in each preparation example was dried, and approximately 0.2 g of the obtained dried material was pressed for 2 minutes under pressing conditions of a temperature of 200°C and a pressure of 5 MPa to obtain a film. The obtained film was cut into a 1 cm square to serve as a test specimen, and the mass W2 (g) of the test specimen was measured. Subsequently, the test specimen was immersed in an electrolyte (a solution in which LiPF6 is dissolved at a concentration of 1 mol / L in a mixed solvent with a volume ratio of ethylene carbonate / diethyl carbonate = 3 / 7) at a temperature of 60°C for 72 hours. Afterward, the test specimen was removed from the electrolyte, the mixed solvent on the surface was wiped off, and the mass W3 (g) of the test specimen was measured. Then, the degree of swelling (%) was calculated according to the following formula.

[0232] Electrolyte swelling degree (%) = W3 / W2 × 100

[0233] <Mass per unit area of ​​the adhesive layer>

[0234] In the description, the mass per unit area of ​​the adhesive layer was determined from the difference in mass per unit area between before supplying the adhesive layer composition and after supplying and drying the adhesive layer composition.

[0235] <Coating rate of the adhesive layer>

[0236] Using a laser microscope (manufactured by Keyence, VR-3100), the distance between the centers of the dots (pitch) x and y, and the radius of the dots r were measured in an area where the adhesive material was arranged (coated) in a dot pattern. Then, using these values, the coverage rate of the adhesive layer was calculated by the following equation (2).

[0237] Coverage rate of the adhesive layer = {πr 2 / (x·y)} × 100(%)···(2)

[0238] Pressure sensitivity of adhesion

[0239] The composition for a non-aqueous secondary battery adhesive layer prepared in each example and comparative example is coated onto the roughened side of a PET substrate (Unitica's polyester film PTHA-25) using a bar coater, and then dried at 50°C for 2 minutes, so that after drying, the mass per unit area on the PET substrate is 4 to 5 g / m² 2 A thin film was formed. Afterward, a PE separator (manufactured by Asahi Kasei, ND412, surface roughness Sa: 0.10 ~ 0.20 μm) cut to 10 × 50 mm was superimposed on the film and pressed using a precision press machine under conditions of a temperature of 25°C, a pressure of 1 MPa, and a pressing time of 10 seconds to prepare an evaluation sample. Subsequently, the evaluation sample was fixed by attaching the PE separator side to the base of a peel test device (load cell) with double-sided tape, and the PET substrate was pulled at a speed of 50 mm / min at a peel angle of 90° to measure the peel strength. The peel strength was measured in the same manner for the evaluation sample that was precision pressed under conditions of a temperature of 25°C, a pressure of 3 MPa, and a pressing time of 10 seconds. The difference between the peel strength when pressing at a pressure of 3 MPa and the peel strength when pressing at a pressure of 1 MPa was divided by 2 was defined as "pressure sensitivity".

[0240] Inkjet Ejection Characteristics

[0241] For the compositions for non-aqueous secondary battery adhesive layers prepared in each example and comparative example, a discharge test was performed using a high-performance head-mounted discharge test kit (IJK-200S, manufactured by Microjet). The discharge characteristics were then evaluated according to the following criteria.

[0242] A: Dispensing is possible, and re-dispensing is possible even if the standby time is 5 minutes or more.

[0243] B: Discharge is possible, but re-discharge becomes impossible after a 5-minute pause.

[0244] C: Discharge impossible

[0245] <Adhesion between electrode and separator>

[0246] Under the same conditions as each example and comparative example, a negative electrode and a separator coated with an adhesive layer (adhesive material) on one side were pressed for 10 seconds under pressing conditions of a temperature of 25°C and a pressure of 2 MPa, and a laminate after lamination (i.e., a laminate formed by laminating one negative electrode and one separator with an adhesive material interposed therebetween) was taken and used as a test specimen.

[0247] This test specimen was placed with the negative electrode collector side facing downward, and cellophane tape was attached to the surface of the negative electrode collector side. At this time, the cellophane tape specified in JIS Z1522 was used. In addition, the cellophane tape was fixed to a horizontal test stand. Then, the stress was measured when one end of the separator was pulled vertically upward at a tensile speed of 50 mm / min and detached.

[0248] This measurement was performed a total of 6 times, and the average stress value was calculated as the peel strength. The adhesion between the negative electrode and the separator was evaluated according to the following criteria. A higher peel strength indicates higher adhesion between the electrode (negative electrode) and the separator.

[0249] A: Peel strength of 5.0 N / m or higher

[0250] B: Peel strength 3.0 N / m or more and less than 5.0 N / m

[0251] C: Peel strength 1.0 N / m or more and less than 3.0 N / m

[0252] D: Peel strength 0.5 N / m or more and less than 1.0 N / m

[0253] E: Peel strength less than 0.5 N / m

[0254] <Lithium deposition rate on the negative electrode surface>

[0255] The manufactured lithium-ion secondary battery was fully charged to a State of Charge (SOC) of 100% using a constant current of 1C under an environment of -10℃. In addition, the fully charged secondary battery was disassembled to remove the negative electrode, and the surface condition of the negative electrode composite layer was observed. Then, the area of ​​lithium deposited on the surface of the negative electrode composite layer was measured, and the lithium deposition rate on the negative electrode surface was calculated as = (Area of ​​deposited lithium / Area of ​​the surface of the negative electrode composite layer) × 100 (%). Then, it was evaluated according to the following criteria. A lower lithium deposition rate on the negative electrode surface indicates that lithium deposition on the negative electrode surface during charging is suppressed.

[0256] A: Lithium precipitation rate is less than 10%

[0257] B: Lithium precipitation rate is 10% or more and less than 15%

[0258] C: Lithium precipitation rate is 15% or more and less than 20%

[0259] D: Lithium precipitation rate of 20% or more

[0260] <Output Characteristics>

[0261] A cell was prepared by charging the fabricated lithium-ion secondary battery to 4.3V using the Constant Current Constant Voltage (CCCV) method under an atmosphere of 25°C. The prepared cell was discharged to 3.0V using the constant current method at 0.2C and 1C under an atmosphere of -10°C, and the electrical capacity was calculated. Then, the discharge capacity retention rate, expressed as the ratio of electrical capacities (= (electrical capacity at 1C / electric capacity at 0.2C) × 100(%)), was calculated. These measurements were performed on five lithium-ion secondary battery cells, and the average value of the calculated discharge capacity retention rates was used as the output characteristic and evaluated according to the following criteria. A higher value indicates superior output characteristics.

[0262] A: Average discharge capacity retention rate is 80% or higher

[0263] B: Average discharge capacity retention rate is 70% or higher and less than 80%

[0264] C: Average discharge capacity retention rate is 60% or more and less than 70%

[0265] D: Average discharge capacity retention rate is less than 60%

[0266] <Increase in Resistance during Cycle Test>

[0267] After securing the fabricated lithium-ion secondary battery with a pressure jig to achieve a surface pressure of 1 MPa, a cycle test was conducted at 45°C. The cycle test conditions were set to 1C CC+CV charging (4.3V, 1 / 50C Cut) and 1C CC discharging (3.0V Cut), and the charge-discharge cycle was repeated 500 times. Afterward, the temperature was lowered to 25°C while the pressure jig was secured, and the output characteristics were measured in the same manner as described in the <Output Characteristics> above. The resistance retention rate (%) before and after the cycle (= discharge capacity retention rate after cycle test / discharge capacity retention rate before cycle test × 100) was calculated and evaluated according to the following criteria. A higher resistance retention rate before and after the cycle indicates a smaller increase in resistance during the cycle test.

[0268] A: Resistance retention rate of 80% or higher

[0269] B: Resistance retention rate is 60% or more and less than 80%

[0270] C: Resistance retention rate is 40% or more and less than 60%

[0271] D: Resistance retention rate less than 40%

[0272] (Preparation Example 1)

[0273] <Preparation of Particulate Polymer 1>

[0274] 100 parts of ion-exchanged water and 0.3 parts of ammonium persulfate were supplied to a reactor equipped with a stirrer, the gas phase was replaced with nitrogen gas, and the temperature was raised to 80°C. Meanwhile, in another container, 40 parts of ion-exchanged water, 0.2 parts of sodium dodecylbenzenesulfonate as an emulsifier, 28.3 parts of styrene as an aromatic monovinyl monomer, 66.6 parts of 2-ethylhexyl acrylate as a monofunctional (meth)acrylic acid ester monomer, 3 parts of methacrylic acid as an acid group-containing monomer, and 0.1 parts of ethylene glycol dimethacrylate as a crosslinking monomer were mixed to obtain a monomer composition for forming a core part. This monomer composition for forming a core part was continuously added to the reactor over a period of 3 hours, and a polymerization reaction was carried out at a temperature of 80°C. By continuing polymerization until the polymerization conversion rate reached 95%, an aqueous dispersion containing particulate polymer constituting the core part was obtained. Subsequently, a monomer composition for forming the shell part, comprising 1.3 parts of styrene as an aromatic monovinyl monomer, 0.65 parts of butyl acrylate, and 0.05 parts of methacrylic acid as an acidic group-containing monomer, was continuously supplied to this aqueous dispersion over a period of 60 minutes, and polymerization was continued. By cooling and stopping the reaction when the polymerization conversion rate reached 98%, an aqueous dispersion containing particulate polymer 1 was prepared.

[0275] The volume average particle size, degree of swelling, and glass transition temperature of the obtained particulate polymer 1 were measured. The results are shown in Table 1.

[0276] In addition, by observing the cross-sectional structure of the particulate polymer using a transmission electron microscope (TEM), it was confirmed that the particulate polymer has a core-shell structure in which the shell part partially covers the outer surface of the core part.

[0277] (Preparation Example 2)

[0278] <Preparation of Particulate Polymer 2>

[0279] In the preparation of the particulate polymer of Preparation Example 1, an aqueous dispersion of particulate polymer 2 having a core-shell structure was prepared in the same manner as Preparation Example 1, except that 0.02 parts of sodium dodecylbenzenesulfonate as an emulsifier was added to 100 parts of ion-exchanged water and 0.3 parts of ammonium persulfate in a reactor equipped with a stirrer. Then, various measurements were performed in the same manner as Preparation Example 1. The results are shown in Table 1.

[0280] (Preparation Example 3)

[0281] <Preparation of Particulate Polymer 3>

[0282] In the preparation of the particulate polymer of Preparation Example 2, an aqueous dispersion of particulate polymer 3 having a core-shell structure was prepared in the same manner as Preparation Example 2, except that the amount of sodium dodecylbenzenesulfonate added to a reactor equipped with a stirrer was changed from 0.02 parts to 0.04 parts. Then, various measurements were performed in the same manner as Preparation Example 1. The results are shown in Table 1.

[0283] (Preparation Example 4)

[0284] <Preparation of Particulate Polymer 4>

[0285] An aqueous dispersion of a particulate polymer 4 having a core-shell structure was prepared in the same manner as in Preparation Example 2, except that in the preparation of the particulate polymer of Preparation Example 2, a shell-forming monomer composition comprising 1.9 parts of styrene as an aromatic monovinyl monomer and 0.1 parts of methacrylic acid as an acidic group-containing monomer was used instead of a shell-forming monomer composition comprising 1.3 parts of styrene as an aromatic monovinyl monomer, 0.65 parts of butyl acrylate, and 0.05 parts of methacrylic acid as an acidic group-containing monomer. Then, various measurements were performed in the same manner as in Preparation Example 1. The results are shown in Table 1.

[0286] (Preparation Example 5)

[0287] <Preparation of Particulate Polymer 5>

[0288] In the preparation of the particulate polymer of Preparation Example 2, instead of a monomer composition for forming a core part comprising 28.3 parts of styrene as an aromatic monovinyl monomer, 66.6 parts of 2-ethylhexyl acrylate as a monofunctional (meth)acrylic acid ester monomer, 3 parts of methacrylic acid as an acid group-containing monomer, and 0.1 parts of ethylene glycol dimethacrylate as a crosslinking monomer, a monomer composition for forming a core part comprising 27.4 parts of styrene as an aromatic monovinyl monomer, 64.5 parts of 2-ethylhexyl acrylate as a monofunctional (meth)acrylic acid ester monomer, 3 parts of methacrylic acid as an acid group-containing monomer, and 0.1 parts of ethylene glycol dimethacrylate as a crosslinking monomer is used, while simultaneously 1.3 parts of styrene as an aromatic monovinyl monomer and butyl acrylate An aqueous dispersion of particulate polymer 5 having a core-shell structure was prepared in the same manner as in Preparation Example 2, except that instead of a shell-forming monomer composition comprising 0.65 parts styrene and 0.05 parts methacrylic acid as an acidic group-containing monomer, a shell-forming monomer composition comprising 4.9 parts styrene as an aromatic monovinyl monomer and 0.1 parts methacrylic acid as an acidic group-containing monomer was used. Then, various measurements were performed in the same manner as in Preparation Example 1. The results are shown in Table 1.

[0289] (Preparation Example 6)

[0290] <Preparation of Particulate Polymer 6>

[0291] In the preparation of the particulate polymer of Preparation Example 2, instead of a monomer composition for forming a core part comprising 28.3 parts of styrene as an aromatic monovinyl monomer, 66.6 parts of 2-ethylhexyl acrylate as a monofunctional (meth)acrylic acid ester monomer, 3 parts of methacrylic acid as an acid group-containing monomer, and 0.1 parts of ethylene glycol dimethacrylate as a crosslinking monomer, a monomer composition for forming a core part comprising 24.5 parts of styrene as an aromatic monovinyl monomer, 57.9 parts of 2-ethylhexyl acrylate as a monofunctional (meth)acrylic acid ester monomer, 2.5 parts of methacrylic acid as an acid group-containing monomer, and 0.1 parts of ethylene glycol dimethacrylate as a crosslinking monomer is used, while simultaneously 1.3 parts of styrene as an aromatic monovinyl monomer and butyl acrylate An aqueous dispersion of particulate polymer 6 having a core-shell structure was prepared in the same manner as in Preparation Example 2, except that instead of a shell-forming monomer composition comprising 0.65 parts styrene and 0.05 parts methacrylic acid as an acidic group-containing monomer, a shell-forming monomer composition comprising 14.8 parts styrene as an aromatic monovinyl monomer and 0.2 parts methacrylic acid as an acidic group-containing monomer was used. Then, various measurements were performed in the same manner as in Preparation Example 1. The results are shown in Table 1.

[0292] (Preparation Example 7)

[0293] <Preparation of Particulate Polymer 7>

[0294] In the preparation of the particulate polymer of Preparation Example 2, instead of a monomer composition for forming a core part comprising 28.3 parts of styrene as an aromatic monovinyl monomer, 66.6 parts of 2-ethylhexyl acrylate as a monofunctional (meth)acrylic acid ester monomer, 3 parts of methacrylic acid as an acid group-containing monomer, and 0.1 parts of ethylene glycol dimethacrylate as a crosslinking monomer, a monomer composition for forming a core part comprising 31.1 parts of styrene as an aromatic monovinyl monomer, 63.8 parts of 2-ethylhexyl acrylate as a monofunctional (meth)acrylic acid ester monomer, 3 parts of methacrylic acid as an acid group-containing monomer, and 0.1 parts of ethylene glycol dimethacrylate as a crosslinking monomer is used, while simultaneously 1.3 parts of styrene as an aromatic monovinyl monomer and butyl acrylate An aqueous dispersion of particulate polymer 7 having a core-shell structure was prepared in the same manner as in Preparation Example 2, except that instead of a shell-forming monomer composition comprising 0.65 parts styrene and 0.05 parts methacrylic acid as an acidic group-containing monomer, a shell-forming monomer composition comprising 1.9 parts styrene as an aromatic monovinyl monomer and 0.1 parts methacrylic acid as an acidic group-containing monomer was used. Then, various measurements were performed in the same manner as in Preparation Example 1. The results are shown in Table 1.

[0295] (Preparation Example 8)

[0296] <Preparation of Particulate Polymer 8>

[0297] In the preparation of the particulate polymer of Preparation Example 2, instead of a monomer composition for forming a core part comprising 28.3 parts of styrene as an aromatic monovinyl monomer, 66.6 parts of 2-ethylhexyl acrylate as a monofunctional (meth)acrylic acid ester monomer, 3 parts of methacrylic acid as an acid group-containing monomer, and 0.1 parts of ethylene glycol dimethacrylate as a crosslinking monomer, a monomer composition for forming a core part comprising 18.9 parts of styrene as an aromatic monovinyl monomer, 75.2 parts of butyl acrylate as a monofunctional (meth)acrylic acid ester monomer, 2.9 parts of methacrylic acid as an acid group-containing monomer, and 1 part of ethylene glycol dimethacrylate as a crosslinking monomer is used, and at the same time, 1.3 parts of styrene as an aromatic monovinyl monomer and 0.65 parts of butyl acrylate, An aqueous dispersion of particulate polymer 8 having a core-shell structure was prepared in the same manner as in Preparation Example 2, except that instead of a shell-forming monomer composition containing 0.05 parts of methacrylic acid as an acidic group-containing monomer, a shell-forming monomer composition containing 1.9 parts of styrene as an aromatic monovinyl monomer and 0.1 parts of methacrylic acid as an acidic group-containing monomer was used. Then, various measurements were performed in the same manner as in Preparation Example 1. The results are shown in Table 1.

[0298] (Preparation Example 9)

[0299] <Preparation of Particulate Polymer 9>

[0300] In a reactor equipped with a stirrer, 90 parts of ion-exchanged water and 0.5 parts of ammonium persulfate were supplied, respectively, the gas phase was replaced with nitrogen gas, and the temperature was raised to 80°C. Meanwhile, in another container, 15 parts of ion-exchanged water, 1.0 parts of Neopelex G15 (manufactured by Kao Chemical Co., Ltd.) as an emulsifier, 70.0 parts of 2-ethylhexyl acrylate as a monofunctional (meth)acrylic acid ester monomer, 25.0 parts of styrene as an aromatic monovinyl monomer, 1.7 parts of allylglycidyl ether and 0.3 parts of allyl methacrylate as crosslinkable monomers, and 3.0 parts of acrylic acid as an acid group-containing monomer were mixed to obtain a monomer composition.

[0301] Polymerization was carried out by continuously adding this monomer composition to the reactor over a period of 4 hours. During the continuous addition, the reaction was carried out at a temperature of 80°C. After the continuous addition was finished, the reaction was stopped by stirring for another 3 hours at a temperature of 80°C.

[0302] After cooling the obtained aqueous dispersion to a temperature of 25°C, an aqueous sodium hydroxide solution was added to adjust the pH to 8.0, and then steam was introduced to remove unreacted monomers, thereby obtaining an aqueous dispersion of particulate polymer 9 that does not have a core-shell structure. Various measurements were then performed in the same manner as in Preparation Example 1. The results are shown in Table 1.

[0303] (Preparation Example 10)

[0304] <Preparation of Particulate Polymer 10>

[0305] In a reactor equipped with a stirrer, 90 parts of ion-exchanged water, 0.05 parts of sodium dodecylbenzenesulfonate (manufactured by Kao Chemical Co., Ltd., “Neoplex G-15”) as an emulsifier, and 0.23 parts of ammonium persulfate were each supplied, the gas phase was replaced with nitrogen gas, and the temperature was raised to 70°C.

[0306] Meanwhile, in another container, a monomer composition was obtained by mixing 50 parts of ion-exchanged water, 0.1 parts of sodium dodecylbenzenesulfonate as an emulsifier, 2.5 parts of methacrylic acid (MAA) as a monomer containing acidic functional groups, 10 parts of acrylonitrile (AN) as a (meth)acrylonitrile monomer, 85.3 parts of n-butyl acrylate (BA) as a monofunctional (meth)acrylic acid ester monomer, 0.2 parts of allyl methacrylate (AMA) as a crosslinking monomer, and 2.0 parts of acrylamide (Aam) as a (meth)acrylamide monomer. This monomer composition was continuously added to the above reactor over a period of 4 hours to carry out polymerization. During the addition, the reaction was carried out at 80°C. After the addition was finished, the reaction was terminated by stirring at 80°C for 3 more hours. An aqueous dispersion containing particulate polymer 10, which does not have a core-shell structure, was prepared. Various measurements were then performed in the same manner as in Preparation Example 1. The results are shown in Table 1.

[0307] (Comparative Manufacturing Example 1)

[0308] <Preparation of Particulate Polymer 11>

[0309] In the preparation of the particulate polymer of Preparation Example 2, instead of a monomer composition for forming a core part comprising 28.3 parts of styrene as an aromatic monovinyl monomer, 66.6 parts of 2-ethylhexyl acrylate as a monofunctional (meth)acrylic acid ester monomer, 3 parts of methacrylic acid as an acid group-containing monomer, and 0.1 parts of ethylene glycol dimethacrylate as a crosslinking monomer, a monomer composition for forming a core part comprising 20.2 parts of styrene as an aromatic monovinyl monomer, 47.6 parts of 2-ethylhexyl acrylate as a monofunctional (meth)acrylic acid ester monomer, 2.1 parts of methacrylic acid as an acid group-containing monomer, and 0.1 parts of ethylene glycol dimethacrylate as a crosslinking monomer is used, while simultaneously 1.3 parts of styrene as an aromatic monovinyl monomer and butyl acrylate An aqueous dispersion of particulate polymer 11 having a core-shell structure was prepared in the same manner as in Preparation Example 2, except that instead of a shell-forming monomer composition containing 0.65 parts of styrene and 0.05 parts of methacrylic acid as an acidic group-containing monomer, a shell-forming monomer composition containing 29.7 parts of styrene as an aromatic monovinyl monomer and 0.3 parts of methacrylic acid as an acidic group-containing monomer was used. Then, various measurements were performed in the same manner as in Preparation Example 1. The results are shown in Table 1.

[0310] (Comparative Manufacturing Example 2)

[0311] <Preparation of Particulate Polymer 12>

[0312] In the preparation of the particulate polymer of Preparation Example 2, instead of using a core-forming monomer composition comprising 28.3 parts of styrene as an aromatic monovinyl monomer, 66.6 parts of 2-ethylhexyl acrylate as a monofunctional (meth)acrylic acid ester monomer, 3 parts of methacrylic acid as an acid group-containing monomer, and 0.1 parts of ethylene glycol dimethacrylate as a crosslinking monomer, a core-forming monomer composition comprising 28.9 parts of styrene as an aromatic monovinyl monomer, 68 parts of 2-ethylhexyl acrylate as a monofunctional (meth)acrylic acid ester monomer, 3 parts of methacrylic acid as an acid group-containing monomer, and 0.1 parts of ethylene glycol dimethacrylate as a crosslinking monomer is used, and the shell-forming monomer composition is not supplied; otherwise, the process is the same as Preparation Example 2, resulting in a polymer having no core-shell structure. An aqueous dispersion of particulate polymer 12 was prepared. Then, various measurements were performed in the same manner as in Preparation Example 1. The results are shown in Table 1.

[0313] (Comparative Manufacturing Example 3)

[0314] <Preparation of Particulate Polymer 13>

[0315] In the preparation of the particulate polymer of Preparation Example 2, instead of a monomer composition for forming a core part comprising 28.3 parts of styrene as an aromatic monovinyl monomer, 66.6 parts of 2-ethylhexyl acrylate as a monofunctional (meth)acrylic acid ester monomer, 3 parts of methacrylic acid as an acid group-containing monomer, and 0.1 parts of ethylene glycol dimethacrylate as a crosslinking monomer, a monomer composition for forming a core part comprising 28.6 parts of styrene as an aromatic monovinyl monomer, 67.3 parts of 2-ethylhexyl acrylate as a monofunctional (meth)acrylic acid ester monomer, 3 parts of methacrylic acid as an acid group-containing monomer, and 0.1 parts of ethylene glycol dimethacrylate as a crosslinking monomer is used, while simultaneously 1.3 parts of styrene as an aromatic monovinyl monomer and butyl acrylate An aqueous dispersion of particulate polymer 13 having a core-shell structure was prepared in the same manner as in Preparation Example 2, except that instead of a shell-forming monomer composition containing 0.65 parts styrene and 0.05 parts methacrylic acid as an acidic group-containing monomer, a shell-forming monomer composition containing 0.95 parts styrene as an aromatic monovinyl monomer and 0.05 parts methacrylic acid as an acidic group-containing monomer was used. Then, various measurements were performed in the same manner as in Preparation Example 1. The results are shown in Table 1.

[0316] (Comparative Manufacturing Example 4)

[0317] <Preparation of Particulate Polymer 14>

[0318] An aqueous dispersion of a particulate polymer 14 having a core-shell structure was prepared in the same manner as in Preparation Example 1, except that instead of a monomer composition for forming a core part comprising 28.3 parts of styrene as an aromatic monovinyl monomer, 66.6 parts of 2-ethylhexyl acrylate as a monofunctional (meth)acrylic acid ester monomer, 3 parts of methacrylic acid as an acidic group-containing monomer, and 0.1 parts of ethylene glycol dimethacrylate as a crosslinking monomer, a monomer composition for forming a core part comprising 56.5 parts of styrene as an aromatic monovinyl monomer, 38.4 parts of 2-ethylhexyl acrylate as a monofunctional (meth)acrylic acid ester monomer, 3 parts of methacrylic acid as an acidic group-containing monomer, and 0.1 parts of ethylene glycol dimethacrylate as a crosslinking monomer was used. Then, various measurements were performed in the same manner as in Preparation Example 1. The results are shown in Table 1.

[0319] (Comparative Manufacturing Example 5)

[0320] Preparation of particulate polymer 15)

[0321] In a 5 MPa pressure vessel equipped with a stirrer, 60 parts of 2-ethylhexyl acrylate, 15 parts of styrene, and 5 parts of methacrylic acid were added as monomer compositions used for manufacturing the core part, along with 1 part of sodium dodecylbenzenesulfonate and 150 parts of ion-exchanged water as emulsifiers, and 0.5 parts of potassium persulfate as a polymerization initiator, and the mixture was stirred thoroughly. Subsequently, the temperature was raised to 60°C to initiate polymerization. By continuing the polymerization until the polymerization conversion rate reached 96%, an aqueous dispersion containing particulate polymer constituting the core part was obtained.

[0322] Next, 20 parts of styrene were continuously added to this aqueous dispersion as a monomer composition used for the preparation of the shell part, and polymerization was continued by heating to 70°C. By stopping the reaction by cooling when the polymerization conversion rate reached 96%, an aqueous dispersion containing a particulate polymer 15 having a core-shell structure was prepared. Then, various measurements were performed in the same manner as in Preparation Example 1. The results are shown in Table 1.

[0323] (Example 1)

[0324] <Preparation of a composition for an adhesive layer>

[0325] An aqueous dispersion of particulate polymer 1 obtained in Preparation Example 1 and an aqueous dispersion of particulate polymer 9 obtained in Preparation Example 9 were mixed such that the mass ratio of the solid content was 100:10, and ion-exchanged water was further added to dilute the mixture to a solid content concentration of 10.5%. Additionally, propylene glycol was added to the obtained mixture to adjust the solid content concentration to 10%, thereby obtaining a composition for an adhesive layer.

[0326] Production of Bu-geuk Fabric

[0327] In a 5 MPa pressure vessel equipped with a stirrer, 33 parts of 1,3-butadiene, 3.5 parts of itaconic acid, 63.5 parts of styrene, 0.4 parts of sodium dodecylbenzenesulfonate as an emulsifier, 150 parts of ion-exchanged water, and 0.5 parts of potassium persulfate as a polymerization initiator were added and stirred thoroughly, after which the temperature was raised to 50°C to initiate polymerization. When the polymerization conversion rate reached 96%, the reaction was stopped by cooling to obtain a mixture containing a binder (SBR) for the negative electrode composite layer. A 5% aqueous sodium hydroxide solution was added to the mixture containing the binder for the negative electrode composite layer to adjust the pH to 8, and unreacted monomers were removed by heated vacuum distillation. Subsequently, the mixture was cooled to 30°C or lower to obtain an aqueous dispersion containing the desired binder for the negative electrode composite layer.

[0328] Next, 100 parts of artificial graphite (volume average particle size: 15.6 μm) as a negative electrode active material, 1 part (equivalent to solid content) of a 2% aqueous solution of sodium carboxymethylcellulose salt (manufactured by Nippon Paper Co., Ltd., product name "MAC350HC") as a viscosity modifier, and ion-exchanged water were mixed to adjust the solid content concentration to 68%, and then mixed for 60 minutes at a temperature of 25°C. Additionally, the solid content concentration was adjusted to 62% with ion-exchanged water, and then mixed for 15 minutes at a temperature of 25°C. To the obtained mixture, 1.5 parts (equivalent to solid content) of an aqueous dispersion containing the binder for the negative electrode composite layer described above and ion-exchanged water were added to adjust the final solid content concentration to 52%, and then mixed for 10 minutes. This was subjected to degassing under reduced pressure to obtain a non-aqueous secondary battery negative electrode slurry composition with good fluidity.

[0329] The obtained slurry composition for a non-aqueous secondary battery negative electrode was applied using a comma coater onto both sides of a copper foil with a thickness of 20 μm, which serves as a current collector, such that the film thickness after drying was approximately 150 μm, and then dried. This drying was performed by conveying the copper foil through an oven at a temperature of 60°C at a speed of 0.5 m / min for 2 minutes. Subsequently, the negative electrode material was heat-treated at a temperature of 120°C for 2 minutes to obtain a negative electrode material before pressing. This negative electrode material before pressing was rolled using a roll press to obtain a negative electrode material after pressing with a negative electrode composite layer thickness of 80 μm.

[0330] Production of the original fabric

[0331] 100 parts of LiCoO2 with a volume average particle size of 12 μm as a positive electrode active material, 2 parts of acetylene black (manufactured by Denka Corporation, product name “HS-100”) as a conductive material, 2 parts of polyvinylidene fluoride (manufactured by Kureha Corporation, product name “#7208”) as a binder in terms of solid content, and N-methylpyrrolidone as a solvent were mixed to make the total solid content concentration 70%. These were mixed using a planetary mixer to obtain a slurry composition for a positive electrode of a non-aqueous secondary battery.

[0332] The obtained slurry composition for a non-aqueous secondary battery positive electrode was applied using a comma coater onto both sides of a 20 μm thick aluminum foil current collector so that the film thickness after drying was approximately 150 μm, and then dried. This drying was performed by conveying the aluminum foil through an oven at a temperature of 60°C at a speed of 0.5 m / min for 2 minutes. Subsequently, the material was heat-treated at a temperature of 120°C for 2 minutes to obtain a positive electrode substrate.

[0333] Then, by rolling the obtained positive electrode material using a roll press, a post-press positive electrode material having a positive electrode composite layer was obtained.

[0334] <Preparation of Separator Fabric>

[0335] A polyethylene (PE) separator fabric (product name: Asahi Kasei manufactured "ND412") was prepared.

[0336] Manufacture of Laminated Bodies

[0337] A laminate was fabricated using the fabricated adhesive layer composition, negative electrode fabric, positive electrode fabric, and separator fabric as shown in FIG. 3. Meanwhile, in FIG. 3, reference numeral 91 represents a conveyor roller, and reference numeral 92 represents a heat roller.

[0338] Specifically, while conveying the negative electrode fabric (20A) unwound from the negative electrode fabric roll at a speed of 10 m / min, an adhesive layer composition is supplied from the inkjet head of an inkjet coating machine (52) (manufactured by Konica, KM1024 (shear mode type)) onto one surface of the negative electrode fabric (20A), and the second separator fabric (30A) unwound from the separator fabric roll and the negative electrode fabric (20A) are bonded together using compression rollers (61, 62). Additionally, a composition for an adhesive layer was supplied from the inkjet head of an inkjet coating machine (51) (manufactured by Konica, KM1024 (shear mode type)) on the other side of the negative electrode fabric (20A), and the laminate of the first separator fabric (10A) unwound from the separator fabric roll, the negative electrode fabric (20A), and the second separator fabric (30A) was laminated using compression rollers (61, 62). Additionally, on the surface opposite to the negative electrode (20A) side of the first separator fabric (10A), an adhesive layer composition was supplied from the inkjet head of an inkjet coating machine (53) (manufactured by Konica, KM1024 (shear mode type)), and a pre-cut positive electrode (40) was placed, and then the laminate of the first separator fabric (10A), the negative electrode fabric (20A), and the second separator fabric (30A) and the positive electrode (40) were bonded together using compression rollers (61, 62). Then, an adhesive layer composition was supplied onto the positive electrode (40) from the inkjet head of an inkjet coating machine (54) (manufactured by Konica, KM1024 (shear mode type)), and then cut with a cutter (70) to obtain a laminate formed by stacking the second separator, the negative electrode, the first separator, and the positive electrode in this order. Here, at the ends of the respective current collectors of the positive electrode (40) and negative electrode (20A), a portion is formed where the electrode composite layer (positive electrode composite layer or negative electrode composite layer) is not formed, and a tab of a desired size is formed in advance, and lamination is performed so that the positive electrode tab and the negative electrode tab are placed on the same single edge side of the bonding surface X and Y of the electrode and separator.

[0339] Meanwhile, bonding using compression rollers (61, 62) was performed at a temperature of 25°C and a pressure of 2 MPa.

[0340] In addition, the supplied adhesive layer composition was dried by using a heat roller (92) on a part of the conveyor roller (91) (drying temperature: 70℃, drying time: 1 second).

[0341] Here, the adhesive layer composition from the coating machine (51 to 54) was supplied so that the adhesive layer composition formed a uniform dot pattern. The dot size had a diameter of 100 μm, and the spacing was a pitch of 400 μm. The mass per unit area of ​​the adhesive material was 0.2 g / m² 2 It was. In addition, the coverage rate was measured to be 6.5%.

[0342] Manufacturing of secondary batteries

[0343] In addition, five of the laminates fabricated above were stacked and pressed at a temperature of 25°C and a pressure of 2 MPa for 10 seconds to produce a stacked body. This stacked body was then wrapped in an aluminum packaging material as an outer casing, and an electrolyte (solvent: ethylene carbonate / diethyl carbonate / vinylene carbonate = 68.5 / 30 / 1.5 (volume ratio), electrolyte: 1M concentration LiPF6) was injected. Subsequently, the opening of the aluminum packaging material was closed with a heat seal at a temperature of 150°C to fabricate a stacked lithium-ion secondary battery with a capacity of 800 mAh. The lithium deposition rate on the negative electrode surface, output characteristics, and resistance increase during a cycle test of the obtained secondary battery were evaluated. The results are shown in Table 2.

[0344] (Example 2)

[0345] In preparing the adhesive layer composition of Example 1, the aqueous dispersion of particulate polymer 2 obtained in Preparation Example 2 was used instead of the aqueous dispersion of particulate polymer 1 obtained in Preparation Example 1, in the same manner as in Example 1, to produce and prepare the adhesive layer composition, negative electrode material, positive electrode material, separator material, laminate, and secondary battery.

[0346] Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.

[0347] (Example 3)

[0348] In preparing the adhesive layer composition of Example 1, the aqueous dispersion of particulate polymer 3 obtained in Preparation Example 3 was used instead of the aqueous dispersion of particulate polymer 1 obtained in Preparation Example 1, in the same manner as in Example 1, to produce and prepare the adhesive layer composition, negative electrode material, positive electrode material, separator material, laminate, and secondary battery.

[0349] Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.

[0350] (Example 4)

[0351] In preparing the adhesive layer composition of Example 1, the aqueous dispersion of particulate polymer 4 obtained in Preparation Example 4 was used instead of the aqueous dispersion of particulate polymer 1 obtained in Preparation Example 1, in the same manner as in Example 1, to produce and prepare the adhesive layer composition, negative electrode material, positive electrode material, separator material, laminate, and secondary battery.

[0352] Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.

[0353] (Example 5)

[0354] In preparing the composition for the adhesive layer of Example 1, the aqueous dispersion of particulate polymer 5 obtained in Preparation Example 5 was used instead of the aqueous dispersion of particulate polymer 1 obtained in Preparation Example 1, in the same manner as in Example 1, to produce and prepare the composition for the adhesive layer, the negative electrode material, the positive electrode material, the separator material, the laminate, and the secondary battery.

[0355] Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.

[0356] (Example 6)

[0357] In preparing the adhesive layer composition of Example 1, the aqueous dispersion of particulate polymer 6 obtained in Preparation Example 6 was used instead of the aqueous dispersion of particulate polymer 1 obtained in Preparation Example 1, in the same manner as in Example 1, to produce and prepare the adhesive layer composition, negative electrode material, positive electrode material, separator material, laminate, and secondary battery.

[0358] Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.

[0359] (Example 7)

[0360] In preparing the adhesive layer composition of Example 1, the aqueous dispersion of particulate polymer 7 obtained in Preparation Example 7 was used instead of the aqueous dispersion of particulate polymer 1 obtained in Preparation Example 1, in the same manner as in Example 1, to produce and prepare the adhesive layer composition, negative electrode material, positive electrode material, separator material, laminate, and secondary battery.

[0361] Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.

[0362] (Example 8)

[0363] In preparing the adhesive layer composition of Example 1, the aqueous dispersion of particulate polymer 8 obtained in Preparation Example 8 was used instead of the aqueous dispersion of particulate polymer 1 obtained in Preparation Example 1, in the same manner as in Example 1, to produce and prepare the adhesive layer composition, negative electrode material, positive electrode material, separator material, laminate, and secondary battery.

[0364] Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.

[0365] (Example 9)

[0366] In preparing the adhesive layer composition of Example 1, the aqueous dispersion of particulate polymer 10 obtained in Preparation Example 10 was used instead of the aqueous dispersion of particulate polymer 9 obtained in Preparation Example 9, in the same manner as in Example 1, to produce and prepare the adhesive layer composition, negative electrode material, positive electrode material, separator material, laminate, and secondary battery.

[0367] Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.

[0368] (Example 10)

[0369] A composition for an adhesive layer, a negative electrode material, a positive electrode material, a separator material, a laminate, and a secondary battery were prepared and prepared in the same manner as in Example 1, except that a polypropylene (PP) separator material (product name Cellguard #2500) was used instead of a polyethylene (PE) separator material (product name "ND412" manufactured by Asahi Kasei).

[0370] Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.

[0371] (Comparative Example 1)

[0372] In preparing the composition for the adhesive layer of Example 1, the aqueous dispersion of particulate polymer 11 obtained in Comparative Preparation Example 1 was used instead of the aqueous dispersion of particulate polymer 1 obtained in Preparation Example 1, in the same manner as in Example 1, to produce and prepare the composition for the adhesive layer, the negative electrode material, the positive electrode material, the separator material, the laminate, and the secondary battery.

[0373] Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.

[0374] (Comparative Example 2)

[0375] In preparing the adhesive layer composition of Example 1, the aqueous dispersion of particulate polymer 12 obtained in Comparative Preparation Example 2 was used instead of the aqueous dispersion of particulate polymer 1 obtained in Preparation Example 1, in the same manner as in Example 1, to produce and prepare the adhesive layer composition, negative electrode fabric, positive electrode fabric, and separator fabric.

[0376] Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 2. As a result of evaluating the inkjet ejection characteristics of the adhesive layer composition in the same manner as in Example 1, the adhesive layer composition could not be ejected. Therefore, it was not possible to manufacture a laminate and a secondary battery.

[0377] (Comparative Example 3)

[0378] In preparing the composition for the adhesive layer of Example 1, the aqueous dispersion of particulate polymer 13 obtained in Comparative Preparation Example 3 was used instead of the aqueous dispersion of particulate polymer 1 obtained in Preparation Example 1, in the same manner as in Example 1, to produce and prepare the composition for the adhesive layer, the negative electrode material, the positive electrode material, the separator material, the laminate, and the secondary battery.

[0379] Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.

[0380] (Comparative Example 4)

[0381] In preparing the composition for the adhesive layer of Example 1, the aqueous dispersion of particulate polymer 14 obtained in Comparative Preparation Example 4 was used instead of the aqueous dispersion of particulate polymer 1 obtained in Preparation Example 1, in the same manner as in Example 1, to produce and prepare the composition for the adhesive layer, the negative electrode material, the positive electrode material, the separator material, the laminate, and the secondary battery.

[0382] Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.

[0383] (Comparative Example 5)

[0384] In preparing the composition for the adhesive layer of Example 1, the aqueous dispersion of particulate polymer 15 obtained in Comparative Preparation Example 5 was used instead of the aqueous dispersion of particulate polymer 1 obtained in Preparation Example 1, in the same manner as in Example 1, to produce and prepare the composition for the adhesive layer, the negative electrode material, the positive electrode material, the separator material, the laminate, and the secondary battery.

[0385] Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.

[0386] In Tables 1 and 2 below,

[0387] "MMA" represents methyl methacrylate, and

[0388] "BA" represents butyl acrylate,

[0389] "2EHA" represents 2-ethylhexyl acrylate, and

[0390] "AN" represents acrylonitrile,

[0391] "St" represents styrene,

[0392] "MAA" represents methacrylic acid,

[0393] "AA" represents acrylic acid,

[0394] "Aam" represents acrylamide,

[0395] "AGE" represents allylglycidyl ether,

[0396] "AMA" stands for allyl methacrylate,

[0397] "EDMA" represents ethylene glycol dimethacrylate, and

[0398] "PE" stands for polyethylene,

[0399] "PP" stands for polypropylene.

[0400]

[0401]

[0402] As can be seen from the results shown in Table 2, in Examples 1 to 10 using a composition for a non-aqueous secondary battery adhesive layer with a pressure sensitivity value of adhesive strength greater than 20 and less than 80, it can be seen that inkjet ejection characteristics, adhesive strength, and battery characteristics (output characteristics, increase in resistance during cycle testing) can be achieved at high levels. In contrast, in Comparative Examples 1 to 5 using a composition for a non-aqueous secondary battery adhesive layer with a pressure sensitivity value of adhesive strength outside the range of greater than 20 and less than 80, it can be seen that inkjet ejection characteristics, adhesive strength, and battery characteristics (output characteristics, increase in resistance during cycle testing) cannot be achieved at high levels.

[0403] It is inferred that the reason the adhesive strength is deteriorated in Example 6 is that the mass ratio of the shell portion, which has a high glass transition temperature, is high.

[0404] It is inferred that the reason the battery characteristics in Example 8 are slightly deteriorated is because the butyl acrylate monomer content of the particulate polymer is high, and the degree of swelling is high.

[0405] It is inferred that the reason the adhesive strength is slightly worse in Example 10 is that the polypropylene separator has higher hydrophobicity than the polyethylene separator.

[0406] Industrial applicability

[0407] According to the present invention, an adhesive layer for a non-aqueous secondary battery can be provided that secures inkjet ejection characteristics and can firmly bond battery components together under room temperature pressure, and a composition for an adhesive layer for a non-aqueous secondary battery can also be provided that exhibits excellent battery characteristics in a non-aqueous secondary battery.

[0408] In addition, according to the present invention, an adhesive layer for a non-aqueous secondary battery can be provided that firmly bonds battery members together by applying pressure at room temperature and also exhibits excellent electrical characteristics in the non-aqueous secondary battery.

[0409] In addition, according to the present invention, a laminate for a non-aqueous secondary battery can be provided that exhibits excellent electrical characteristics in a non-aqueous secondary battery.

[0410] In addition, according to the present invention, a non-aqueous secondary battery with excellent electrical characteristics can be provided.

[0411] In addition, according to the present invention, a method for manufacturing an adhesive layer for a non-aqueous secondary battery can be provided, which firmly bonds battery members together by applying pressure at room temperature and also enables excellent electrical characteristics for the non-aqueous secondary battery.

[0412] In addition, according to the present invention, a method for manufacturing a laminate for a non-aqueous secondary battery capable of exhibiting excellent electrical characteristics in a non-aqueous secondary battery can be provided. Explanation of the symbols

[0413] 10A 1st Separator Fabric 20A negative pole material 30A 2nd Separator Fabric 40 Straight Drama 50 droplets 51 ~ 54 Coating machine (nozzle head) 61, 62 compression rollers 70 cutters 91 return roller 92 Heat Roller 300 particulate polymers 310 core section Outer surface of the 310S core 320 Shellbu

Claims

Claim 1 A composition for a non-aqueous secondary battery adhesive layer comprising a particulate polymer, wherein the value of the pressure sensitivity of the adhesive force obtained by the following formula (1) is greater than 20 and less than 80, and the particulate polymer has a core-shell structure comprising a core portion and a shell portion covering the outer surface of the core portion, wherein the glass transition temperature of the core portion is -50°C or higher and 25°C or lower, the glass transition temperature of the shell portion is 50°C or higher and 200°C or lower, and the mass ratio of the shell portion to the total of the core portion and the shell portion is 2 mass% or higher and 15 mass% or lower. Pressure sensitivity of the adhesive force (N / (m·MPa)) = (T3 - T1) / 2···(1) (wherein T1 is the polyethylene separator and the non-aqueous secondary battery adhesive layer obtained from the composition for a non-aqueous secondary battery adhesive layer, when the non-aqueous secondary battery adhesive layer obtained from the polyethylene separator and the composition for a non-aqueous secondary battery adhesive layer is pressure-bonded at 25°C and a pressure of 1 MPa for 10 seconds. T3 represents the adhesion strength (N / m) of the adhesive layer for a non-aqueous secondary battery, and represents the adhesion strength (N / m) of the polyethylene separator and the adhesive layer for a non-aqueous secondary battery obtained from the polyethylene separator and the composition for the adhesive layer for a non-aqueous secondary battery when the adhesive layer is pressure-bonded at 25°C and a pressure of 3 MPa for 10 seconds. Claim 2 A composition for a non-aqueous secondary battery adhesive layer according to claim 1, wherein the glass transition temperature of the core portion is -40℃ or higher and 25℃ or lower. Claim 3 A composition for a non-aqueous secondary battery adhesive layer according to claim 1, wherein the volume average particle size of the particulate polymer is 100 nm or more and 1500 nm or less. Claim 4 An adhesive layer for a non-aqueous secondary battery, formed using a composition for an adhesive layer for a non-aqueous secondary battery described in any one of claims 1 to 3. Claim 5 A method for manufacturing an adhesive layer for a non-aqueous secondary battery, comprising: a process of coating a composition for an adhesive layer for a non-aqueous secondary battery described in any one of claims 1 to 3 onto a substrate by an inkjet method; and a process of drying the composition for an adhesive layer for a non-aqueous secondary battery coated on the substrate. Claim 6 A laminate for a non-aqueous secondary battery comprising an electrode and a separator, wherein the electrode and the separator are bonded together via an adhesive layer for a non-aqueous secondary battery described in claim 4. Claim 7 A method for manufacturing a laminate for a non-aqueous secondary battery, comprising: a process of supplying an adhesive material to at least one bonding surface among an electrode and a separator; and a process of bonding the electrode and the separator by applying pressure at room temperature through the bonding surface to which the adhesive material was supplied, wherein the adhesive material is formed using a composition for a non-aqueous secondary battery adhesive layer described in any one of claims 1 to 3. Claim 8 A non-aqueous secondary battery having a laminate for a non-aqueous secondary battery as described in paragraph 6. Claim 9 delete

Citation Information

Patent Citations

  • Composition for nonaqueous secondary battery function layers, base with function layer for nonaqueous secondary batteries, method for producing laminate for nonaqueous secondary batteries, and nonaqueous secondary battery

    KR1020170039620A